Optoelectronic device
Patent Information
- Application Number
- CN202011637707.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2040-12-31
AI Technical Summary
Existing technologies struggle to simultaneously improve the photoelectric efficiency and lifetime performance of quantum dot light-emitting display devices (QLEDs).
By employing core-shell quantum dot materials in QLED devices, with the outer shell being ZnSeS, a hole injection barrier with a valence band top energy level difference of more than 0.5 eV is constructed. An appropriate energy level difference is set between the hole transport layer and the quantum dot light-emitting layer to balance the injection efficiency of holes and electrons and avoid carrier accumulation.
This achieves a balance between hole and electron injection in QLED devices under stable operating conditions, thereby improving the luminous efficiency and lifespan of the devices.
Smart Images

Figure CN114695725B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of display technology, and in particular relates to an optoelectronic device. Background Technology
[0002] Quantum dot light-emitting diode (QLED) display technology is a rapidly emerging new display technology in recent years. Similar to organic light-emitting diode (OLED) displays, QLED is an active-matrix light-emitting technology, thus sharing advantages such as high luminous efficiency, fast response speed, high contrast, and wide viewing angles. Due to the superior material properties of quantum dots in QLED display technology, QLED has performance advantages over OLED in many aspects. For example, quantum dots offer continuously adjustable light emission with an extremely narrow emission width, enabling a wider color gamut and higher purity display; the inorganic material properties of quantum dots give QLED better device stability; QLED devices require lower driving voltages than OLEDs, achieving higher brightness and further reducing energy consumption; and QLED display technology is compatible with the production processes and technologies of printed displays, enabling large-size, low-cost, and rollable high-efficiency mass production. Therefore, QLED is considered one of the preferred technologies for the next generation of thin, portable, flexible, transparent, and high-performance display screens.
[0003] Due to the similarity in light-emitting principles between QLED and OLED display technologies, the device structure of QLED currently borrows heavily from OLED technology during its development. Aside from replacing organic light-emitting materials with quantum dot materials in the light-emitting layer, other functional layer materials, such as the charge injection layer or charge transport layer, often utilize materials already found in OLEDs. Furthermore, the explanation of device physics in QLED devices, the selection and matching principles of energy levels for functional layer materials, all follow the existing theoretical framework of OLEDs. Applying the classical device physics conclusions obtained from OLED device research to QLED device systems has indeed significantly improved QLED device performance, especially efficiency.
[0004] However, current classic approaches and strategies used in OLEDs cannot effectively improve the lifetime of QLED devices. Furthermore, while these classic OLED approaches and strategies can improve QLED device efficiency, research has shown that the lifetime of these high-efficiency QLED devices is significantly worse than similar devices with lower efficiency. Therefore, existing QLED device structures designed based on OLED device theory cannot simultaneously improve both photoelectric efficiency and lifetime performance. Corresponding to the unique device mechanism of QLED devices, new and more targeted QLED device structures need to be developed. Summary of the Invention
[0005] The purpose of this application is to provide an optoelectronic device that aims to solve, to some extent, the problem that existing technologies cannot simultaneously improve the photoelectric efficiency and lifetime performance of QLED devices.
[0006] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:
[0007] This application provides an optoelectronic device, comprising: an anode, a hole transport layer on the anode, a quantum dot emitting layer on the hole transport layer, and a cathode on the quantum dot emitting layer. The quantum dot emitting layer contains a core-shell structured quantum dot material, the outer shell of the quantum dot material is ZnSeS, and the absolute value of the valence band top energy level of the hole transport material in the hole transport layer is less than or equal to 5.7 eV.
[0008] The optoelectronic device provided in this application, with the quantum dot material's outer shell layer specifically being ZnSeS, utilizes the energy level and other characteristics of ZnSeS to design an optimal structure for the optoelectronic device. Specifically, since the outer shell layer of the quantum dot in this embodiment uses ZnSeS, and the valence band energy level is between ZnSe and ZnS, a valence band top energy level difference (ΔE) needs to be constructed. EML-HTL If the hole injection barrier is greater than or equal to 0.5 eV, then the valence band top energy level of the hole transport material needs to be less than or equal to 5.7 eV. By constructing a hole injection barrier, the hole injection rate is reduced, the injection efficiency of electrons and holes in the luminescent layer is balanced, carrier accumulation is avoided, and the luminescence efficiency is improved. Attached Figure Description
[0009] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0010] Figure 1 This is a schematic diagram of the structure of the optoelectronic device provided in the first aspect of this application;
[0011] Figure 2 This is a schematic diagram of the structure of the optoelectronic device provided in the second aspect of this application;
[0012] Figure 3 This is a schematic diagram of the structure of the optoelectronic device provided in the third aspect of this application;
[0013] Figure 4 This is a schematic diagram of the structure of the optoelectronic device provided in the fourth aspect of this application;
[0014] Figure 5 This is a schematic diagram of the structure of the optoelectronic device provided in the fifth aspect of this application;
[0015] Figure 6 This is a schematic diagram of the structure of the optoelectronic device provided in the sixth aspect of this application;
[0016] Figure 7 This is a schematic diagram of the structure of the optoelectronic device provided in the seventh aspect of this application;
[0017] Figure 8 This is a schematic diagram of the structure of the optoelectronic device provided in the eighth aspect of this application;
[0018] Figure 9 This is a schematic diagram of the structure of the optoelectronic device provided in the ninth aspect of this application;
[0019] Figure 10 This is a schematic diagram of the structure of the optoelectronic device provided in the tenth aspect of this application;
[0020] Figure 11 This is a schematic diagram of the structure of the optoelectronic device provided in the eleventh aspect of this application;
[0021] Figure 12 This is a schematic diagram of the structure of the optoelectronic device provided in the twelfth aspect of this application;
[0022] Figure 13 This is a schematic diagram of the structure of the optoelectronic device provided in aspect thirteen of this application;
[0023] Figure 14 This is a schematic diagram of the positive structure of a quantum dot light-emitting diode provided in an embodiment of this application;
[0024] Figure 15 This is a schematic diagram of the inversion structure of a quantum dot light-emitting diode provided in an embodiment of this application;
[0025] Figure 16 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in Embodiments 1 to 7 of this application;
[0026] Figure 17 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in Embodiments 8-9 of this application;
[0027] Figure 18 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in Embodiments 10-11 of this application;
[0028] Figure 19 These are the voltage-time variation graphs of quantum dot light-emitting diodes provided in Embodiments 12-14 of this application;
[0029] Figure 20 These are the voltage-time variation graphs of quantum dot light-emitting diodes provided in Embodiments 15-19 of this application;
[0030] Figure 21 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in Embodiments 20-25 of this application;
[0031] Figure 22 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in Embodiments 26-28 of this application;
[0032] Figure 23 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in Embodiments 29-31 of this application;
[0033] Figure 24 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in embodiments 32-35 of this application;
[0034] Figure 25 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in embodiments 36-38 of this application;
[0035] Figure 26 These are the voltage-time variation graphs of the quantum dot light-emitting diodes provided in embodiments 39-41 of this application;
[0036] Figure 27 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in embodiments 39 to 41 of this application;
[0037] Figure 28 These are the voltage-time variation graphs of the quantum dot light-emitting diodes provided in embodiments 42-43 of this application;
[0038] Figure 29 These are test diagrams of the luminous lifetime of quantum dot light-emitting diodes provided in embodiments 42-43 of this application. Detailed Implementation
[0039] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0040] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0041] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0042] It should be understood that, in the various embodiments of this application, the sequence numbers of the above processes do not imply a sequential order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application. The terminology used in the embodiments of this application is for the purpose of describing specific embodiments only and is not intended to limit this application. The singular forms "a" and "the" used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0043] In the embodiments of this application, ΔE HTL-HIL =E HOMO,HTL -E HIL ΔE EML-HTL =E HOMO,EML -E HTL All energy level / work function values are taken as absolute values. A larger absolute value indicates a deeper energy level, and a smaller absolute value indicates a shallower energy level.
[0044] The key to this application lies in simultaneously improving the lifetime and photoelectric efficiency of QLED devices. Currently, there is a significant difference between testing device lifetime and characterizing device efficiency: device efficiency testing is usually short, thus characterizing the instantaneous state of the QLED device at the start of operation; while device lifetime characterizes the ability of the device to maintain its efficiency after continuous operation and entering a stable state.
[0045] Currently, based on the existing theoretical framework of traditional OLED devices, it is believed that the rate of electron injection into the emissive layer is generally faster than that of holes. Therefore, to balance and improve the recombination efficiency of holes and electrons in the emissive layer of QLED devices, hole injection layers are typically incorporated into the device, and the injection barrier between adjacent functional layers is minimized to enhance hole injection efficiency, thereby improving carrier injection efficiency and reducing interface charge accumulation. However, this method can only improve the photoelectric efficiency of QLED devices to a certain extent at the initial moment, but it cannot simultaneously improve device lifetime, and may even reduce it. Through the gradual and in-depth research on the mechanism of QLED devices, this application has discovered that the use of quantum dot materials and other nanomaterials with special material surfaces in the QLED device system gives QLEDs some special mechanisms that differ from those of OLED devices. These mechanisms are closely related to the performance of QLED devices, especially their lifetime.
[0046] Specifically, this application reveals that in the initial operating state of a QLED device, the electron injection rate in the emissive layer is faster than the hole injection rate, resulting in a negative charge on the quantum dot material. This negative charge is maintained due to the structural characteristics of the quantum dot material, the binding effect of surface ligands, and the Coulomb blocking effect. However, the negative charge of the quantum dot material makes further electron injection increasingly difficult during continuous operation of the QLED device, leading to an imbalance between the actual electron and hole injection in the emissive layer. Furthermore, as the QLED device continues to operate until a stable state is reached, the negative charge of the quantum dot material also tends to stabilize, meaning that the electrons newly captured and bound by the quantum dots reach a dynamic equilibrium with the electrons consumed by radiative transitions. At this point, the electron injection rate into the emissive layer is much lower than in the initial state, and the actual hole injection rate required to achieve charge injection balance in the emissive layer is also relatively low. If the hole injection efficiency is improved based on the theoretical framework of traditional OLED devices, using a deep-level hole transport layer can only achieve an instantaneous charge injection balance at the initial stage of QLED device operation, thus achieving high device efficiency at the initial moment. However, as QLED devices reach a stable operating state, excessive hole injection exacerbates the imbalance between electrons and holes in the light-emitting layer, causing the QLED device efficiency to decrease. Furthermore, this charge imbalance intensifies with continued operation, leading to a rapid decline in the QLED device's lifetime.
[0047] Therefore, to achieve carrier injection balance in the light-emitting layer of the device and obtain devices with higher efficiency and longer lifespan, the key to finely controlling the carrier injection of holes and electrons on both sides of the device lies in two aspects: First, controlling the hole injection rate to a lower level so that the hole injection rate is balanced with the electron injection rate in the stable operating state of the QLED device, thereby improving the recombination efficiency of the QLED device. Second, since the hole injection rate required for the actual stable operating state of QLED devices is lower than traditionally expected, carrier accumulation is prone to occur, causing irreversible damage to the device. Therefore, it is essential to minimize the impact of carrier accumulation on device lifespan and improve the device's lifespan.
[0048] As attached Figure 1 As shown, the first aspect of this application provides an optoelectronic device, including: an anode, a hole transport layer on the anode, a quantum dot light-emitting layer on the hole transport layer, and a cathode on the quantum dot light-emitting layer. The quantum dot light-emitting layer includes a core-shell structured quantum dot material, and the energy difference between the outer shell material of the quantum dot material and the valence band top energy level of the hole transport material in the hole transport layer is greater than or equal to 0.5 eV.
[0049] The optoelectronic device provided in the first aspect of this application establishes a valence band top energy level difference greater than or equal to 0.5 eV between the outer shell material and the hole transport material of the quantum dot material, i.e., E EML-HTL ≥0.5 eV. By increasing the hole injection barrier, the hole injection efficiency is reduced, thereby balancing the injection of holes and electrons in the emitting layer. Based on the energy level characteristics of current hole transport materials and the energy level characteristics of the shell material of quantum dot materials, this application has found that at least ΔE is required. EML-HTL A potential barrier of ≥0.5 eV is required to significantly reduce hole injection efficiency and achieve a balance between electron and hole injection efficiency in the emitting layer. Furthermore, the ΔE in this application... EML-HTL A hole injection barrier of ≥0.5eV does not prevent hole injection because the energy levels of the outer shell of the quantum dot will bend when the quantum dot is powered on, and charge carriers can be injected through tunneling. Therefore, although the increase of this energy level barrier will reduce the charge carrier injection rate, it will not completely prevent the final injection of charge carriers.
[0050] Quantum dot materials are generally composed of semiconductor compounds from groups II-IV, II-VI, II-V, III-V, III-VI, IV-VI, I-III-VI, II-IV-VI, and II-IV-V of the periodic table, or core-shell structures composed of at least two of these semiconductor compounds. In some embodiments, the core-shell quantum dot material includes a core and an outer shell layer. In other embodiments, the core-shell quantum dot material includes a core, an outer shell layer, and an intermediate bridge layer located between the core and the outer shell layer. The intermediate bridge layer can be one layer or multiple layers. In the core-shell quantum dot material, the core material determines the luminescence performance, while the outer shell material protects the stability of the core's luminescence and facilitates carrier injection. Electrons and holes are injected into the core through the outer shell layer to emit light. Generally, the band gap of the core is narrower than that of the outer shell, so the energy difference between the hole transport material and the valence band level of the quantum dot core is smaller than the energy difference between the hole transport material and the valence band level of the quantum dot outer shell. Therefore, in the embodiments of this application, ΔE EML-HTL A voltage greater than or equal to 0.5 eV can simultaneously ensure the effective injection of hole carriers into the core of the quantum dot material. The specific structure and material type of the core-shell quantum dot material described in this application will be further described in later embodiments according to different application scenarios.
[0051] In some embodiments, the energy difference between the valence band top of the outer shell material of the quantum dot material and the hole transport material in the hole transport layer is 0.5–1.7 eV, i.e., ΔE EML-HTL The energy level barrier, ranging from 0.5 eV to 1.7 eV, established between the outer shell material and the hole transport material of a quantum dot material, is applicable to device systems constructed from different hole transport materials and quantum dot materials, optimizing the injection balance of electrons and holes in various device systems. In practical applications, different top valence band energy differences ΔE can be set according to the specific material properties. EML-HTL In this case, the carrier injection rates of holes and electrons on both sides of the light-emitting layer are precisely controlled to balance the injection of holes and electrons.
[0052] In some specific embodiments, the energy difference between the outer shell material of the quantum dot material and the valence band top energy level of the hole transport material is 0.5eV to 0.7eV. In this case, the hole transport material can be TFB, P12, or P15, and the quantum dot shell material can be ZnSe or CdS, such as TFB-ZnSe, P12 / P15-CdS and other device systems.
[0053] In some specific embodiments, the energy difference between the outer shell material of the quantum dot material and the valence band top energy level of the hole transport material is 0.7 eV to 1.0 eV. In this case, the hole transport material can be TFB or PO9, and the quantum dot shell material can be ZnSe or CdS, such as PO9-ZnSe, TFB-CdS and other device systems.
[0054] In some specific embodiments, the energy difference between the outer shell material of the quantum dot material and the valence band top energy level of the hole transport material is 1.0 eV to 1.4 eV. In this case, the hole transport material can be TFB, PO9, P13, or P14, and the quantum dot shell material can be CdS, ZnSe, or ZnS, such as TFB-ZnS, PO9-CdS, P13 / P14-ZnSe and other device systems.
[0055] In some specific embodiments, the energy difference between the outer shell material and the hole transport material of the quantum dot material is greater than 1.4 eV to 1.7 eV. In this case, device systems such as PO9-ZnS and P13 / P14-ZnS can be used.
[0056] On the one hand, since hole injection layers in current devices are often used to improve hole injection efficiency, while the QLED devices in some embodiments of this application require controlling the hole injection rate to a lower level through certain methods, a hole injection layer may not be provided in some specific embodiments of the optoelectronic devices provided in the first aspect of this application.
[0057] On the other hand, the hole injection layer in QLED devices not only improves hole injection efficiency but also regulates stable and balanced hole injection, which is one of the key factors affecting device performance and lifespan. Therefore, embodiments of this application can further control hole injection efficiency and reduce the impact of charge accumulation on device lifespan by setting a hole injection layer in the device. Specifically:
[0058] Typically, QLED device performance research focuses on interface damage caused by charge accumulation at the interfaces of the EML (Emitting Layer), such as the HTL (High-Level Layer) or ETL (Electronic Level Layer), and the quenching of excitons in the EML. However, the energy level barrier at the HIL-HTL interface is also prone to charge accumulation, leading to irreversible damage to the interface under the influence of an electric field. This results in increased device voltage and decreased brightness. Furthermore, the voltage increase caused by this is significantly different from the voltage increase caused by charge accumulation at the EML interface: the damage caused by the electric field generated by charge accumulation at the HIL-HTL interface is usually irreversible and continues to worsen as the device remains powered; whereas charge accumulation at the EML interface is reversible and reaches a certain saturation point. Therefore, charge accumulation at the HIL-HTL interface has a greater impact on device lifetime and other performance characteristics.
[0059] On the one hand, in order to reduce the irreversible damage to device lifetime performance caused by charge accumulation at the HIL and HTL interface, the embodiments of this application optimize the carrier injection and recombination efficiency within the QLED device. (See attached...) Figure 2As shown, in a second aspect of the present application, an optoelectronic device is provided based on or independently of the first aspect embodiment described above. The optoelectronic device includes a first hole injection layer, which is located between an anode layer and a hole transport layer. The absolute value of the difference between the valence band top energy level of the hole transport layer material and the work function of the first hole injection material in the first hole injection layer is less than or equal to 0.2 eV.
[0060] The optoelectronic device provided in the second aspect of this application, by limiting |ΔE HTL-HIL A voltage less than or equal to 0.2 eV significantly reduces the hole injection barrier between the HTL and HIL, improving hole injection efficiency from the anode and facilitating effective hole injection from HIL to HTL. This eliminates the barrier and interface charge, reduces the overall device resistance, and consequently reduces irreversible damage caused by charge accumulation at the HIL-HTL interface, lowering the device drive voltage and extending device lifetime. If |ΔE HTL-HIL If the voltage is greater than 0.2 eV, the interface energy level barrier between HIL and HTL is prone to charge accumulation, which causes irreversible damage to the interface between HIL and HTL under the action of electric field, resulting in an increase in device voltage and a decrease in device brightness.
[0061] In some embodiments, the absolute value of the difference between the valence band top energy level of the hole transport layer material and the work function of the first hole injection material is 0 eV. |ΔE of this application embodiment HTL-HIL When | is 0, the effective injection of holes from HIL to HTL is good, the barrier and interface charge are eliminated, the overall resistance of the device is reduced, thereby reducing the device driving voltage and improving the device life.
[0062] In some embodiments, the absolute value of the work function of the first hole injection material is 5.3 eV to 5.6 eV. This work function value is close to the absolute value of the valence band energy level of conventional hole transport materials (around 5.4 eV), which is beneficial for controlling |ΔE|. HTL-HIL In a lower range, the energy levels of the two components are made essentially level, eliminating potential barriers and interface charges, reducing device drive voltage, and improving device lifetime. In this application's embodiments, by selecting HIL and HTL materials with suitable energy levels, |ΔE HTL-HIL | ≤0.2eV can effectively eliminate the energy level barrier between HIL and HTL, as well as the charge accumulation at the interface, thereby reducing irreversible damage at the interface between HIL and HTL.
[0063] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -4 cm 2 / Vs. The embodiments of this application employ a mobility higher than 1×10⁻⁶. -4 cm 2Through extensive experiments, the inventors discovered that hole transport materials with the above mobility can improve hole transport and migration, prevent charge accumulation, eliminate interface charge, and better reduce device drive voltage and improve device lifespan.
[0064] On the other hand, the embodiments of this application aim to reduce the hole injection rate within the QLED device, regulate the carrier injection and recombination efficiency, and simultaneously reduce the irreversible damage to device lifetime performance caused by charge accumulation at the HIL and HTL interface. (See attached...) Figure 3 As shown, in a third aspect of the present application, an optoelectronic device is provided based on or separately from the first aspect of the embodiment described above, including a second hole injection layer. The second hole injection layer is located between the anode layer and the hole transport layer, and the difference between the valence band top energy level of the hole transport layer material and the work function of the second hole injection material in the second hole injection layer is less than -0.2 eV.
[0065] The optoelectronic device provided in the third aspect of this application constructs an injection barrier of less than -0.2 eV, i.e., ΔE, between the hole transport layer material and the second hole injection material. HTL-HIL A voltage <-0.2eV increases the hole injection barrier from the anode to the HIL, thereby reducing the overall hole injection rate within the QLED device and effectively controlling the number of holes entering the device. On one hand, this effectively reduces the rate of hole injection into the emissive layer, balancing the hole-electron injection rate and improving carrier recombination efficiency. On the other hand, it prevents excessive hole injection from causing charge accumulation at the HTL and HIL interface, preventing irreversible damage to device lifetime due to interface charge accumulation. Simultaneously, it forms a hole-blocking barrier from the HTL to the HIL, preventing holes from diffusing into the HIL layer, improving hole utilization, and ensuring effective "survival" of holes before injection into the emissive layer. By ensuring balanced carrier injection under stable operating conditions, and fully and effectively utilizing the injected holes, the device's luminous efficiency is further guaranteed, achieving a simultaneous improvement in both device efficiency and lifetime.
[0066] In some embodiments, the quantum dot light-emitting layer of the optoelectronic device contains a core-shell structured quantum dot material, where the energy difference between the outer shell material and the hole transport material is greater than 0 eV, i.e., ΔE EML-HTL >0, the energy level of the emitting layer is deeper than that of the hole transport layer; at the same time, there is an injection barrier of less than -0.2 eV between the hole transport layer material and the second hole injection material, i.e., ΔE HTL-HIL<-0.2 eV, the energy level of the hole injection layer is deeper than that of the hole transport layer. In this case, a "deep-shallow-deep" energy level structure is formed between the luminescent layer, hole transport layer, and hole injection layer. This allows the holes injected into the hole transport layer to form a hole carrier trap, effectively "storing" the accumulated holes and preventing them from diffusing to other functional layers or interfaces outside the HTL layer. Furthermore, it eliminates the influence of interface charge on the device. While ensuring balanced carrier injection under stable operating conditions, it more fully and effectively utilizes the injected holes, further guaranteeing the device's luminous efficiency and simultaneously improving both device efficiency and lifetime. In some specific embodiments, the energy difference between the outer shell material and the valence band top of the hole transport material is greater than or equal to 0.5 eV; in other specific embodiments, the energy difference between the outer shell material and the valence band top of the hole transport material can also be 0.5 eV to 1.7 eV, i.e., ΔE EML-HTL With a voltage range of 0.5 eV to 1.7 eV, experiments have verified that the hole carrier trap formed in the above embodiments has good performance. In practical applications, the hole carrier trap can more precisely control the injection balance of holes and electrons in the light-emitting layer of the device, thereby improving the carrier recombination efficiency.
[0067] In some embodiments, the work function difference between the valence band top level of the hole transport layer material and the second hole injection material is -0.9 eV to -0.2 eV, ΔE HTL-HIL The potential barrier is between -0.9 eV and -0.2 eV, within which there is a good balance between hole injection and transport. If it is below -0.9 eV, the resistance to hole injection increases, resulting in a decrease in the amount of holes injected, which affects the balanced injection and effective recombination of holes and electrons in the light-emitting layer. If the barrier is greater than -0.2 eV, holes tend to accumulate at the interface and the utilization rate is not high.
[0068] In some embodiments, the absolute value of the work function of the second hole injection material is 5.4 eV to 5.8 eV. In this embodiment, the absolute value of the work function of the second hole injection material is 5.4 eV to 5.8 eV, which is advantageous for forming a hole blocking barrier with an energy level difference of less than -0.2 eV with the hole transport material. Specifically, the absolute value of the valence band of conventional hole transport materials is approximately 5.3-5.4 eV. The second hole injection material with an absolute work function greater than or equal to 5.4 eV can form a negative energy level difference of less than -0.2 eV with the conventional hole transport material, thereby forming a hole blocking barrier, optimizing the hole injection rate, and improving hole utilization.
[0069] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -4 cm 2 / Vs, in this application embodiment, a mobility higher than 1×10 -4 cm 2 / Vs hole transport material further ensures hole transport and migration, prevents charge accumulation, eliminates interface charge, and better reduces device drive voltage and improves device lifespan.
[0070] In the embodiments of the second and third aspects of this application described above, the hole injection material is preferably a metal oxide material. That is, in some specific embodiments, when the optoelectronic device includes a first hole injection layer, the first hole injection material in the first hole injection layer is selected from a metal oxide material. In other specific embodiments, when the optoelectronic device includes a second hole injection layer, the second hole injection material in the second hole injection layer is selected from a metal oxide material. In the embodiments of this application described above, the metal oxide material used for hole injection has better stability and is not acidic. It not only meets the requirements for hole injection in the above embodiments but also does not have a negative impact on adjacent functional layers. This avoids the degradation of device lifetime caused by thermal or electrical effects during device operation of organic hole injection materials, while also avoiding the destructive effect of the acidity of organic hole injection materials on adjacent functional layers.
[0071] In some embodiments, the metal oxide material includes at least one metal nanomaterial selected from tungsten oxide, molybdenum oxide, vanadium oxide, nickel oxide, and copper oxide. These metal nanomaterials have good stability and are not acidic. In practical applications, by adjusting the work function, energy level barriers of different sizes can be constructed with the hole transport layer, which is beneficial for controlling hole injection and transport, improving carrier recombination efficiency, and reducing the impact of charge accumulation on device lifetime.
[0072] In some embodiments, the particle size of the metal oxide material is 2 to 10 nm. Small particle size metal oxide materials are beneficial for depositing a dense and uniform film, improving its bonding tightness with adjacent functional layers, reducing interface resistance, and improving device performance.
[0073] In other embodiments, the hole injection material may also be an organic hole injection material such as poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), HIL2, HIL1-1, HIL1-2, copper phthalocyanine (CuPc), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), or 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzophenanthrene (HATCN). PEDOT:PSS contains the following structural formula: The organic molecule has a work function of -5.1 eV; HIL2 contains the following structural formula: The organic molecule has a work function of -5.6 eV; both HIL1-1 and HIL1-2 contain the following structural formula: The work function of the organic molecules HIL1-1 is -5.4 eV, and that of HIL1-2 is -5.3 eV.
[0074] In some embodiments, the thickness of the first hole injection layer is 10–150 nm. In other embodiments, the thickness of the second hole injection layer is 10–150 nm. The thickness of the hole injection layer in this application can be flexibly adjusted according to actual application requirements, and the hole injection rate can also be effectively adjusted by regulating the thickness of the hole injection layer.
[0075] Furthermore, in order to construct ΔE, the embodiments of this application... EML-HTL A potential barrier of ≥0.5 eV is used to reduce the hole injection rate within QLED devices, thereby controlling carrier injection and recombination efficiency. Simultaneously, it reduces the irreversible damage to device lifetime performance caused by charge accumulation at the HIL and HTL interface. (See attached image) Figure 4 As shown, a fourth aspect of this application provides an optoelectronic device, wherein the hole transport layer of the optoelectronic device comprises at least two hole transport materials, wherein the absolute value of the valence band top energy level of at least one hole transport material is less than or equal to 5.3 eV. In a specific embodiment, the aforementioned at least two hole transport materials include at least one hole transport material with an absolute value of the valence band top energy level less than or equal to 5.3 eV and one hole transport material with an absolute value of the valence band top energy level greater than 5.3 eV.
[0076] The hole transport layer of the optoelectronic device provided in the fourth aspect of this application is a hybrid material layer containing multiple hole transport materials with different valence band top energy levels. At least one of these hole transport materials has a valence band top energy level less than or equal to 5.3 eV, while the shell energy level of conventional quantum dot luminescent materials is often relatively deep (6.0 eV or deeper). Therefore, an energy level difference of greater than or equal to 0.5 eV is formed between the shallow-level hole transport material and the quantum dot shell material. Furthermore, the inclusion of hole transport materials with an absolute valence band top energy level greater than 5.3 eV allows for finer control of the energy level difference between the hole transport material and the luminescent material shell layer. This allows for precise control of the hole injection barrier between the hole transport material and the quantum dot shell layer through the combination of shallow-level hole transport materials with an absolute value less than or equal to 5.3 eV and deep-level hole transport materials with an absolute value greater than 5.3 eV. Simultaneously, the hole mobility in the HTL layer can be adjusted by using hole transport materials of different energy levels, achieving ΔE. EML-HTL An energy level barrier greater than or equal to 0.5 eV can improve the hole injection efficiency by increasing the hole injection barrier, thereby improving the injection balance between holes and electrons in the light-emitting layer, increasing the device's luminous efficiency, and reducing the impact of charge accumulation on device lifetime.
[0077] In some embodiments, the hole transport layer of the optoelectronic device comprises at least two hole transport materials, wherein one hole transport material has an absolute value of its valence band top level less than or equal to 5.3 eV, and the other includes a hole transport material with an absolute value of its valence band top level greater than 5.3 eV and less than 5.8 eV. In some embodiments, the hole transport layer comprises at least three hole transport materials, one hole transport material has an absolute value of its valence band top level less than or equal to 5.3 eV, and the other includes a hole transport material with an absolute value of its valence band top level greater than or equal to 5.3 eV and less than 5.8 eV, and a hole transport material with an absolute value of its valence band top level greater than or equal to 5.8 eV. This application embodiment achieves flexible adjustment of the hole injection barrier by mixing and matching shallow-level and deep-level materials, based on actual application requirements, device system and other factors. This makes the hole injection barrier to the luminescent material greater than or equal to 0.5 eV, reducing the hole injection efficiency and thus balancing the injection of holes and electrons in the luminescent layer. This makes the application flexible and convenient.
[0078] In some embodiments, when the hole transport layer includes a hole transport material with a valence band top energy level greater than 5.3 eV and less than 5.8 eV, the electron transport layer of the optoelectronic device can employ at least one of the following: an organic electron transport material layer, a metal oxide nanoparticle layer such as ZnO nanoparticles, or a sputtered metal oxide layer. In the embodiments of this application, when the hole transport layer includes at least one hole transport material with a valence band top energy level less than or equal to 5.3 eV and a valence band top energy level greater than 5.3 eV and less than 5.8 eV, the hole transport layer has a relatively moderate valence band top energy level and hole mobility. Therefore, it can be well matched with conventional metal oxides such as ZnO or organic electron transport materials, which is beneficial for the regulation of hole and electron charge balance.
[0079] In some embodiments, when the hole transport layer includes a hole transport material with a valence band top energy level greater than or equal to 5.8 eV, the electron transport layer of the optoelectronic device can employ metal oxide nanoparticles, preferably metal oxide nanoparticles with fewer surface group connections. In this embodiment, when the hole transport layer includes a hole transport material with a valence band top energy level greater than 5.8 eV, both the energy level and mobility performance are significantly different from those of hole transport layer materials with shallow valence band top energy levels less than or equal to 5.3 eV. Different mixing ratios can achieve continuous control within a larger window range, making it suitable for QLED device systems where electron injection and transport changes significantly from the initial state to the stable state, such as metal oxide nanoparticles with fewer surface group connections.
[0080] In some embodiments, the hole transport layer is a mixed material layer containing hole transport materials of different energy levels. The mass percentage of hole transport materials with an absolute value of valence band top energy level less than or equal to 5.3 eV is 30-90%. This percentage of shallow-level hole transport materials easily forms a hole injection barrier of greater than or equal to 0.5 eV with the outer shell of the luminescent material. In practical applications, the mixing ratio of materials of different energy levels can be flexibly adjusted according to the depth of the material energy levels. In some specific embodiments, a mass percentage of hole transport materials with an absolute value of valence band top energy level less than or equal to 5.3 eV of 50-60% shows good results.
[0081] In some embodiments, the hole transport layer is a hybrid material layer comprising hole transport materials of different energy levels, wherein at least one hole transport material has a mobility greater than 1×10⁻⁶. -3 cm 2 / Vs, the high mobility of the hole transport material in this application ensures the high transport and migration performance of holes, reducing the impact of hole accumulation at the interface on device performance. Furthermore, the relatively shallow valence band top energy level of the hole transport layer material with high hole mobility further ensures the formation of a suitable energy difference with the quantum dot shell material.
[0082] In some specific embodiments, the hole transport layer is a hybrid material layer containing hole transport materials of different energy levels, wherein at least one hole transport material has a mobility greater than 1×10⁻⁶. -2 cm 2 / Vs. In other specific embodiments, the hole transport layer is a hybrid material layer containing hole transport materials of different energy levels, wherein the mobility of each hole transport material is greater than 1×10 -3 cm 2 / Vs. The embodiments described above further optimize the mobility of the hole transport material while ensuring hole migration efficiency, avoiding charge accumulation from affecting device performance. They also ensure the matching of hole transport materials at different energy levels in the hole transport layer, constructing a hole injection barrier to ensure the formation of ΔE. EML-HTL A potential barrier of ≥0.5 eV is used to optimize the carrier injection balance and recombination efficiency in QLED devices.
[0083] Furthermore, in order to construct ΔE, the embodiments of this application... EML-HTL A potential barrier of ≥0.5 eV is used to reduce the hole injection rate within QLED devices, thereby controlling carrier injection and recombination efficiency. Simultaneously, it reduces the irreversible damage to device lifetime performance caused by charge accumulation at the HIL and HTL interface. (See attached image) Figure 5As shown, a fifth aspect of this application provides an optoelectronic device, wherein the hole transport layer of the optoelectronic device contains at least two hole transport materials, and the absolute value of the valence band top energy level of each hole transport material is less than or equal to 5.3 eV.
[0084] The hole transport layer of the optoelectronic device provided in the fifth aspect of this application is a hybrid material layer containing multiple hole transport materials with different valence band top energy levels. Each hole transport material has a valence band top energy level less than or equal to 5.3 eV, which can form an energy level difference greater than or equal to 0.5 eV with the quantum dot luminescent material with a deeper shell energy level. This allows for finer control of the hole injection barrier between the quantum dot shell layer in the HTL and EML structures, improving the device's ΔE. EML-HTL ≥0.5eV. This achieves optimal charge injection balance and device efficiency maintenance after the QLED device enters a stable operating state, thus optimizing device lifetime. Furthermore, by utilizing the different hole mobilities of hole transport layer materials, which are all materials with shallow valence band top levels, the hole mobility of the mixed hole transport layer can be finely controlled through different mixing ratios.
[0085] In some embodiments, the hole transport layer comprises a mixed material layer of hole transport materials at different energy levels, wherein the mass percentage of each hole transport material is 5% to 95%. By mixing and matching hole transport materials with different energy levels and mobility, the hole mobility and injection barrier of the mixed hole transport layer can be well controlled.
[0086] In some embodiments, the hole transport layer comprises a hybrid material layer of hole transport materials at different energy levels, wherein at least one hole transport material has a mobility greater than 1 × 10⁻⁶. -3 cm 2 / Vs, hole transport layer materials with high hole mobility have relatively shallow valence band top levels. Limiting the mobility of the hole transport material ensures high hole transport performance and also ensures the formation of a more suitable injection barrier, preventing hole accumulation at the interface that could affect device performance. In some embodiments, the mobility of at least one hole transport material in the hole transport layer is higher than 1×10⁻⁶. -2 cm 2 / Vs. In some embodiments, the mobility of each hole transport material in the hole transport layer is greater than 1×10⁻⁶. -3 cm 2 / Vs.
[0087] In some embodiments, when the valence band top energy levels of the hole transport material in the hole transport layer are all less than or equal to 5.3 eV, the electron transport layer of the optoelectronic device uses surface-passivated metal oxide nanoparticles, preferably surface-modified passivated metal oxide nanoparticles. In this application embodiment, when the valence band top energy levels of the hole transport material in the hole transport layer are all less than or equal to 5.3 eV, materials with small changes in electron injection and transport are required. This is suitable for QLED device systems where the differences in electron injection and transport are small from the initial state of the device to the stable state during continuous operation, such as surface-modified passivated metal oxide nanoparticles.
[0088] In the optoelectronic devices of the above embodiments of this application, the hole transport material is selected from at least one of: polymers containing aniline groups, copolymers containing fluorene groups and aniline groups. These hole transport materials have advantages such as high hole transport efficiency, good stability, and easy availability. In practical applications, hole transport materials with appropriate energy level size and mobility can be selected according to actual application requirements. Specifically:
[0089] In some specific embodiments, when a hole transport material with an absolute value of the valence band top energy level less than or equal to 5.3 eV is required in the optoelectronic device, the hole transport material with an absolute value of the valence band top energy level less than or equal to 5.3 eV can be selected from at least one of P09 and P13. The structural formula of P13 is: The structural formula for P09 is:
[0090] In other specific embodiments, when a hole transport material with an absolute value of the valence band top energy level greater than 5.3 eV and less than 5.8 eV is required in the optoelectronic device, the hole transport material with an absolute value of the valence band top energy level greater than 5.3 eV and less than 5.8 eV includes at least one of TFB, poly-TPD, and P11. The structural formula of P11 is: The structural formula of poly-TPD is: The structural formula for TFB is:
[0091] In other specific embodiments, when a hole transport material with an absolute value of the valence band top energy level greater than or equal to 5.8 eV is required in the optoelectronic device, the hole transport material with an absolute value of the valence band top energy level greater than or equal to 5.8 eV includes at least one of P15 and P12. The structural formula of P12 is: The structural formula for P15 is:
[0092] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -4 cm 2 / Vs, high mobility ensures hole transport and migration performance, reducing the impact of charge accumulation on device lifetime.
[0093] In the embodiments described above, the core-shell quantum dot material includes an outer shell layer, a core, and an intermediate shell layer located between the core and the outer shell layer. The valence band top energy level of the core material is shallower than that of the outer shell material; the valence band top energy level of the intermediate shell material is between the valence band top energy levels of the core and the outer shell material. In the core-shell quantum dot material of this embodiment, the core material affects the luminescence performance, the outer shell material protects the stability of the core's luminescence and facilitates carrier injection, and the intermediate shell layer, with its valence band between the core and the outer shell layer, acts as an intermediate transition, facilitating carrier injection. The intermediate shell layer can form a stepped energy level transition from the core to the outer shell layer, which helps to achieve effective carrier injection and confinement, and reduces lattice interface flicker.
[0094] In some embodiments, the outer shell of the quantum dot material comprises at least one or an alloy of at least two of CdS, ZnSe, ZnTe, ZnS, ZnSeS, CdZnS, and PbS. These outer shell materials not only protect the stability of the core's luminescence and facilitate carrier injection into the quantum dot core for luminescence, but also form a ΔE with the HTL layer material. EML-HTL A potential barrier of 0.5 eV or higher is used to increase the hole injection barrier and reduce the hole injection efficiency, thereby balancing the injection of holes and electrons in the light-emitting layer, improving the device's luminous efficiency, and reducing the impact of charge accumulation on device lifetime.
[0095] In some embodiments, the core of the quantum dot material includes at least one of CdSe, CdZnSe, CdZnS, CdSeS, CdZnSeS, InP, InGaP, GaN, GaP, ZnSe, ZnTe, and ZnTeSe. The luminescence performance of the quantum dot material is related to the core material, which ensures that QLED devices emit light in the 400–700 nm visible light range. This not only meets the range required for optoelectronic display applications but also better reflects the beneficial effects of the energy level interactions between these materials.
[0096] In some embodiments, the intermediate shell material is selected from at least one of CdZnSe, ZnSe, CdZnS, CdZnSeS, CdS, and CdSeS. In specific embodiments of this application, the intermediate shell is selected to form a continuous and natural transition in composition from the core to the outer layer. This helps to achieve minimal lattice mismatch and minimal lattice defects among the core, intermediate shell, and outer shell, thereby achieving the optimal luminescence performance of the core-shell quantum dot material itself.
[0097] In some embodiments, the emission peak wavelength range of the quantum dot material is 400–700 nm. On the one hand, this wavelength range is the range required for the application of optoelectronic display devices. On the other hand, the beneficial effects achieved by the energy level interaction of the light-emitting layer in the device within this wavelength range can be better reflected.
[0098] In some embodiments, the outer shell thickness of the quantum dot material is 0.2–6.0 nm, which covers the thickness of conventional outer shells and is widely applicable to QLED devices in different systems. If the outer shell thickness is too large, the rate at which charge carriers are injected into the luminescent quantum dot through tunneling will decrease; while if the outer shell thickness is too small, the outer shell material cannot provide sufficient protection and passivation for the core material, affecting the luminescence performance and stability of the quantum dot material.
[0099] In the embodiments described above, the optoelectronic device further includes an electron transport layer, wherein the electron transport material in the electron transport layer is selected from at least one of: metal oxide transport materials and organic transport materials. Metal oxide materials generally have high electron mobility and can be fabricated into thin films in QLED devices using solution methods or vacuum sputtering. Organic electron transport layer materials can achieve energy level modulation over a wide range and can be fabricated into thin films in QLED devices using vacuum evaporation or solution methods; the solution methods include inkjet printing, spin coating, inkjet printing, slot coating, or screen printing. A more suitable electron transport material can be flexibly selected according to actual application requirements.
[0100] In some embodiments, the metal oxometalate transport material is selected from at least one of zinc oxide, titanium oxide, zinc sulfide, and cadmium sulfide. These metal oxometalate transport materials used in the above embodiments of this application all possess high electron mobility efficiency. In some embodiments, to further improve electron mobility efficiency, the metal oxometalate transport material is selected from at least one of zinc oxide, titanium oxide, zinc sulfide, and cadmium sulfide doped with a metal element, wherein the metal element includes at least one of aluminum, magnesium, lithium, lanthanum, yttrium, manganese, gallium, iron, chromium, and cobalt. These metal elements can further improve the electron mobility efficiency of the material.
[0101] In some embodiments, the particle size of the metal oxometalate transport material is less than or equal to 10 nm. On the one hand, small-particle-size metal oxometalate transport materials are more conducive to depositing dense and uniform electron transport layer films, improving their bonding tightness with adjacent functional layers, reducing interface resistance, and thus improving device performance. On the other hand, small-particle-size metal oxometalate transport materials have wider band gaps, reducing the exciton quenching of quantum dot materials and improving device efficiency.
[0102] In some embodiments, the electron mobility of the metal oxometalate transport material is 10. -2 ~10 -3 cm 2 / Vs, a high-mobility electron transport material, can reduce charge accumulation at the interface layer and improve electron injection and recombination efficiency.
[0103] In some embodiments, the electron mobility of the organic transport material is not less than 10. -4 cm 2 / Vs. In some embodiments, the organic transport material is selected from at least one of: 8-hydroxyquinoline-lithium (Alq3), aluminum octahydroxyquinoline, fullerene derivative PCBM, 3,5-bis(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (BPT), and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi). These organic transport materials can achieve energy level tuning over a wider range, which is more conducive to tuning the energy levels of each functional layer of the device, improving the stability and photoelectric conversion efficiency of the device.
[0104] In some embodiments, the electron transport layer is a stacked composite structure, including at least two sub-electron transport layers. By selecting sub-electron transport layers with different transport mobility efficiencies and energy level modulation characteristics, the electron transport layer properties can be more flexibly controlled, thereby better optimizing device performance.
[0105] In some embodiments, at least one sub-electron transport layer in the electron transport layer is made of a metal oxometalate transport material. In some embodiments, all sub-electron transport layers in the electron transport layer are metal oxides, and the metal oxide materials of different sub-electron transport layers can be the same or different. That is, in a multilayer electron transport layer where all sub-electron transport layers are metal oxides, there can be a sub-electron transport layer containing at least one layer of metal oxide nanoparticles and at least one layer of non-nanoparticle type metal oxide sub-electron transport layers. Alternatively, the sub-electron transport layers can be doped and intrinsic metal oxides (e.g., Mg-doped ZnO + intrinsic ZnO). Alternatively, all sub-electron transport layers can be made of the same type of metal oxide nanoparticles. When all sub-electron transport layers are made of the same type of metal oxide nanoparticles, the electron mobilities of different sub-electron transport layers can be the same or different.
[0106] In some embodiments, at least one sub-electron transport layer in the electron transport layer is made of an organic transport material. In other embodiments, at least one sub-electron transport layer in the electron transport layer is made of a metal oxometalate transport material, and at least one sub-electron transport layer is made of an organic transport material. The metal oxide materials of different sub-electron transport layers can be the same or different; the metal oxide material is preferably a nanoparticle of the corresponding metal oxide. Through the combined effect of the metal oxometalate transport material and the organic transport material in the electron transport layer, the electron transport layer simultaneously possesses high electron mobility and flexibility in energy level matching. This achieves effective control of the energy levels and electron mobility of the electron transport layer, thereby achieving sufficient matching with hole injection. In some specific embodiments, the electron transport layer containing multiple sub-electron transport layers can be a stacked composite structure such as a combination of ZnO nanoparticles + NaF, or a combination of Mg-doped ZnO nanoparticles + NaF.
[0107] In core-shell quantum dot materials, the core material influences the luminescence properties, while the shell material provides protection and facilitates carrier injection. Once the outer shell material is determined, the energy difference between the valence band top of the quantum dot material and the hole transport material can be adjusted to be greater than or equal to 0.5 eV, thus constructing the desired injection barrier. EML-HTL ≥0.5eV optimizes the balance of electron and hole injection efficiency in the light-emitting layer, improving device efficiency and lifespan.
[0108] Furthermore, as shown in the appendix Figure 6 As shown, a sixth aspect of this application provides an optoelectronic device, including a quantum dot light-emitting layer and a hole transport layer. The quantum dot light-emitting layer contains a core-shell structured quantum dot material, and the outer shell of the quantum dot material is ZnSe. The absolute value of the valence band top energy level of the hole transport material in the hole transport layer is less than or equal to 5.4 eV.
[0109] The optoelectronic device provided in the sixth aspect of this application, with the quantum dot material outer shell layer specifically being ZnSe, designs a preferred structure based on the energy level and other characteristics of ZnSe. Specifically, since the valence band energy level of the ZnSe outer shell material is relatively shallow (the absolute value of the energy level is small), to construct a valence band top energy level difference (ΔE... EML-HTL For a hole injection barrier greater than or equal to 0.5 eV, the absolute value of the valence band top energy level of the hole transport material should be less than or equal to 5.4 eV. In this case, ΔE EML-HTL A hole injection barrier of ≥0.5eV was constructed, which reduced the hole injection rate, balanced the injection efficiency of electrons and holes in the luminescent layer, reduced carrier accumulation, and improved luminescence efficiency.
[0110] In some embodiments, the ZnSe shell thickness in the quantum dot material is 2–5 nm. In this application embodiment, because ZnSe has a relatively narrow band gap and a relatively poor ability to confine excitons in the quantum dot core, a thicker ZnSe shell is required to ensure good luminescence efficiency of the quantum dot core luminescent material itself. The preferred shell thickness is 2.0–5.0 nm. If the shell thickness is too large, the rate at which charge carriers are injected into the luminescent quantum dot through tunneling will decrease; conversely, if the shell thickness is too small, the rate at which charge carriers are injected into the luminescent quantum dot through tunneling will increase. However, when the shell thickness is too small, the shell structure will not provide sufficient protection and passivation for the core, thus affecting the luminescence performance and stability of the quantum dot material.
[0111] In some embodiments, the emission peak wavelength of the quantum dot material is 510–640 nm. For blue core-shell quantum dots with shorter emission wavelengths and wider core band gaps, even using a thick ZnSe outer shell layer cannot fully guarantee the luminescence efficiency of the quantum dot material itself. Therefore, the preferred quantum dot luminescent material in this application embodiment should be red or green quantum dots with an emission peak wavelength range of 510–640 nm to better ensure the luminescence efficiency of the quantum dots.
[0112] In some embodiments, the valence band top energy level difference between the ZnSe material and the hole transport material is 0.5–1.0 eV. In this embodiment, because the ZnSe outer shell has a relatively thick preferred thickness, the rate at which charge carriers are injected into the luminescent quantum dot via tunneling is weakened. Therefore, the valence band top energy level difference (ΔE) between the corresponding hole transport layer material and the quantum dot outer shell material is relatively large. EML-HTL The value can be selected between 0.5 and 1.0 eV. If ΔE EML-HTL If the hole size is too large, it will further reduce the efficiency of hole injection into the quantum dot luminescent core, thus affecting the luminescence efficiency of the quantum dot material.
[0113] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is preferably 4.9 eV to 5.4 eV. Within this range, a more suitable hole injection barrier can be constructed with the ZnSe shell material, thereby optimizing the carrier injection and recombination efficiency in the luminescent layer.
[0114] In some specific embodiments, the absolute value of the valence band top energy level of the hole transport material is preferably 4.9 eV to 5.4 eV. At this time, the difference between the valence band top energy level of the ZnSe material and the hole transport material is 0.5 to 1.0 eV.
[0115] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs, since the absolute value of the valence band top energy level of the hole transport material used in this application embodiment is less than or equal to 5.4eV, the energy level is relatively shallow. Hole transport layer materials with shallow valence band top energy levels usually have higher hole mobility, which is beneficial for the effective transport of holes in a hole transport layer film of a certain thickness, reducing the overall resistance of the device, thereby reducing the device driving voltage and improving the device lifetime.
[0116] Furthermore, as shown in the appendix Figure 7 As shown, the seventh aspect of this application provides an optoelectronic device, including a quantum dot light-emitting layer and a hole transport layer. The quantum dot light-emitting layer contains a core-shell structured quantum dot material, the outer shell of which is ZnS. The absolute value of the valence band top energy level of the hole transport material in the hole transport layer is less than or equal to 6.0 eV.
[0117] The optoelectronic device provided in the seventh aspect of this application, with the quantum dot material outer shell layer specifically being ZnS, designs an optimal structure based on the energy level and other characteristics of ZnS. Specifically, the valence band energy level of the ZnS outer shell material is relatively deep (with a larger absolute value compared to ZnSe), and a valence band top energy level difference (ΔE) needs to be constructed. EML-HTL If the valence band top energy level of the hole transport material is greater than or equal to 0.5 eV, then the valence band top energy level of the hole transport material should be less than or equal to 6.0 eV. In this case, ΔE EML-HTL A hole injection barrier of ≥0.5eV was constructed, which reduced the hole injection rate, balanced the injection efficiency of electrons and holes in the luminescent layer, reduced carrier accumulation, and improved luminescence efficiency.
[0118] In some embodiments, the ZnS shell thickness is 0.2–2.0 nm. In this embodiment, because ZnS has a wide band gap and a strong ability to confine excitons in the quantum dot core, a thinner ZnS shell thickness can essentially guarantee the good luminescence efficiency of the quantum dot luminescent material itself; the preferred shell thickness is 0.2–2.0 nm. Simultaneously, the thin ZnS shell can effectively reduce the overall resistance of the device, lower the device driving voltage, and thus improve device performance.
[0119] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is preferably 4.9 eV to 6.0 eV. Within this range, a more suitable hole injection barrier can be constructed with the ZnS shell material, optimizing carrier injection and recombination efficiency in the emitting layer. In some embodiments, the absolute value of the valence band top energy level of the hole transport material is preferably 4.9 eV to 5.5 eV.
[0120] In some embodiments, the valence band top energy level difference between the ZnS material and the hole transport material is 1.0–1.6 eV. In this embodiment, because the ZnS outer shell layer has a relatively thin, preferably thin, carrier injection into the luminescent quantum dot via tunneling is accelerated. Therefore, the valence band top energy level difference (ΔE) between the corresponding hole transport layer material and the quantum dot outer shell material in the quantum dot luminescent layer is significantly increased. EML-HTL The value needs to be appropriately increased to better balance the injection of holes and electrons; its preferred range should be between 1.0 and 1.6 eV. If ΔE EML-HTL If the size is too large, it will further reduce the efficiency of hole injection into the quantum dot luminescent core, thus affecting the luminescence efficiency of the quantum dot material.
[0121] In some embodiments, the emission peak wavelength of the quantum dot material is 400–700 nm. In this application embodiment, because ZnS has a wide band gap and a strong ability to bind excitons in the quantum dot core, it can effectively ensure the luminescence efficiency of the quantum dot material itself. It is applicable to all quantum dot materials in the visible light region with emission peak wavelengths of 400–700 nm, and has a wide range of applications.
[0122] In some embodiments, because the valence band top level of the hole transport material used in this application is relatively deep (less than or equal to 6.0 eV), the hole mobility is relatively low, and the mobility of the hole transport material is higher than 1 × 10⁻⁶. -4 cm 2 / Vs. In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs.
[0123] Furthermore, as shown in the appendix Figure 8 As shown, the eighth aspect of this application provides an optoelectronic device, including a quantum dot light-emitting layer and a hole transport layer. The quantum dot light-emitting layer contains a core-shell structured quantum dot material, the outer shell of which is CdZnS. The absolute value of the valence band top energy level of the hole transport material in the hole transport layer is less than or equal to 5.9 eV.
[0124] The optoelectronic device provided in the eighth aspect of this application, with the quantum dot material's outer shell layer specifically being CdZnS, incorporates a preferred structure designed based on the energy level and other characteristics of CdZnS. Specifically, since the outer shell layer of the quantum dot in this embodiment uses CdZnS, whose valence band energy level is between ZnSe and ZnS, to construct a hole injection barrier with a valence band top energy level difference (ΔEEML-HTL) greater than or equal to 0.5 eV, the valence band top energy level of the hole transport material needs to be less than or equal to 5.9 eV. By constructing this hole injection barrier, the hole injection rate is reduced, the injection efficiency of electrons and holes in the light-emitting layer is balanced, carrier accumulation is reduced, and luminous efficiency is improved.
[0125] In some embodiments, the CdZnS shell thickness is 0.5–3.0 nm. Since the band gap of CdZnS is between that of ZnSe and ZnS, a preferred shell thickness of 0.5–3.0 nm can simultaneously ensure the binding ability of excitons in the quantum dot core and the good luminescence efficiency of the quantum dot luminescent material itself.
[0126] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.9 eV. Within this range, a more suitable hole injection barrier can be constructed with the CdZnS shell material, optimizing carrier injection and recombination efficiency in the luminescent layer. In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.5 eV.
[0127] In some embodiments, the valence band top energy level difference between the CdZnS material and the hole transport material is 0.8–1.4 eV. The valence band top energy level difference (ΔE) between the hole transport layer material and the quantum dot outer shell material in the quantum dot emitting layer in this application embodiment is shown in the figure. EML-HTL The preferred range is 0.8–1.4 eV, which ensures both the efficiency of carrier injection into the luminescent quantum dot via tunneling and a good balance between the injection efficiency of holes and electrons. If ΔE EML-HTL If ΔE is too large, the efficiency of carriers being injected into the luminescent quantum dot core through tunneling will decrease; if ΔE EML-HTL If the value is too small, the injection rate of holes will not be well regulated.
[0128] In some embodiments, the emission peak wavelength of the quantum dot material is 400–700 nm. In this application, because CdZnS has a relatively strong binding ability to excitons in the quantum dot core, it can effectively ensure the luminescence efficiency of the quantum dot material itself. This makes it applicable to all quantum dot materials in the visible light region with emission peak wavelengths of 400–700 nm, thus having a wide range of applications.
[0129] In some embodiments, because the valence band top level of the hole transport material used in this application is relatively deep (less than or equal to 5.9 eV), the hole mobility is relatively low, and the mobility of the hole transport material is higher than 1 × 10⁻⁶. -4 cm 2 / Vs. In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs.
[0130] Furthermore, as shown in the appendix Figure 9 As shown, the ninth aspect of this application provides an optoelectronic device, including a quantum dot light-emitting layer and a hole transport layer. The quantum dot light-emitting layer contains a core-shell structured quantum dot material, the outer shell of which is ZnSeS. The absolute value of the valence band top energy level of the hole transport material in the hole transport layer is less than or equal to 5.7 eV.
[0131] The optoelectronic device provided in the ninth aspect of this application, with the quantum dot material's outer shell layer specifically being ZnSeS, incorporates a preferred structure designed based on the energy level and other characteristics of ZnSeS. Specifically, since the outer shell layer of the quantum dot in this embodiment uses ZnSeS, and its valence band energy level is between ZnSe and ZnS, to construct a hole injection barrier with a valence band top energy level difference (ΔEEML-HTL) greater than or equal to 0.5 eV, the valence band top energy level of the hole transport material needs to be less than or equal to 5.7 eV. By constructing this hole injection barrier, the hole injection rate is reduced, the injection efficiency of electrons and holes in the light-emitting layer is balanced, carrier accumulation is reduced, and luminous efficiency is improved.
[0132] In some embodiments, the ZnSeS shell thickness is 1.0 to 4.0 nm. Since the easily oxidized Se in the ZnSeS shell is closer to the quantum dot surface, the ZnSeS shell needs to be thicker to ensure sufficient protection and passivation for the core. Therefore, the preferred ZnSeS shell thickness is 1.0 to 4.0 nm.
[0133] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.7 eV. Within this range, a more suitable hole injection barrier can be constructed with the ZnSeS shell material, optimizing carrier injection and recombination efficiency in the luminescent layer. In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.4 eV.
[0134] In some embodiments, the valence band top energy level difference between the ZnSeS material and the hole transport material is 0.9–1.4 eV. The valence band top energy level difference (ΔE) between the hole transport layer material and the quantum dot outer shell material in the quantum dot emitting layer of this application embodiment is shown in the figure. EML-HTL When the preferred voltage range is 0.9–1.4 eV, it can ensure the efficiency of carrier injection into the luminescent quantum dot through tunneling, while also achieving a good balance between the injection efficiency of holes and electrons. If ΔE EML-HTL If ΔE is too large, the efficiency of carriers being injected into the luminescent quantum dot core through tunneling will decrease; if ΔE EML-HTL If the value is too small, the injection rate of holes will not be well regulated.
[0135] In some embodiments, the emission peak wavelength of the quantum dot material is 400–700 nm. In this application, because ZnSeS has a relatively strong binding ability to excitons in the quantum dot core, it can effectively ensure the luminescence efficiency of the quantum dot material itself. This makes it suitable for all quantum dot materials in the visible light region with emission peak wavelengths of 400–700 nm, thus having a wide range of applications.
[0136] In some embodiments, because the valence band top level of the hole transport material used in this application is relatively deep (less than or equal to 5.7 eV), the hole mobility is relatively low, and the mobility of the hole transport material is higher than 1 × 10⁻⁶. -4 cm 2 / Vs. In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs.
[0137] In the optoelectronic devices provided in aspects six to nine above of this application, the hole transport material is selected from at least one of: polymers containing aniline groups, copolymers containing fluorene groups and aniline groups. In practical applications, a hole transport material with a suitable mobility can be selected according to specific application requirements.
[0138] In some embodiments, the aniline-containing polymers of hole transport materials with an absolute value of valence band top energy level less than or equal to 5.4 eV include: poly-TPD, P9, TFB, and P13.
[0139] In some embodiments, copolymers containing fluorene and aniline groups with an absolute value of the valence band top energy level of the hole transport material less than or equal to 5.4 eV include: TFB and P13.
[0140] In some embodiments, the aniline-containing polymers of hole transport materials with an absolute value of valence band top energy level greater than 5.4 eV and less than or equal to 5.9 eV include: P11, P12, and P15.
[0141] In some embodiments, copolymers containing fluorene and aniline groups with an absolute value of the valence band top energy level of the hole transport material greater than 5.4 eV and less than or equal to 5.9 eV include: P12 and P15.
[0142] In the optoelectronic devices provided in aspects six to nine of this application, the core-shell structured quantum dot material includes the aforementioned outer shell layer, a core, and an intermediate shell layer located between the core and the outer shell layer; wherein, the valence band top energy level of the core material is shallower than the valence band top energy level of the outer shell material; and the valence band top energy level of the intermediate shell material is between the valence band top energy level of the core material and the valence band top energy level of the outer shell material.
[0143] In some embodiments, the core material is selected from at least one of the following semiconductor compounds: Groups II-IV, II-VI, II-V, III-V, III-VI, IV-VI, I-III-VI, II-IV-VI, and II-IV-V of the periodic table. In some specific embodiments, the core material is selected from at least one of the following: CdSe, CdZnSe, CdSeS, CdZnSeS, InP, InGaP, GaP, ZnTe, and ZnTeSe. These core materials have good luminescent properties and exhibit good compatibility with the outer shell layer ZnSe, ZnS, CdZnS, or ZnSeS.
[0144] In some specific embodiments, the intermediate shell material is selected from at least one of CdZnSe, ZnSe, CdZnS, CdZnSeS, CdS, and CdSeS. The principle for matching the intermediate shells in this application is as follows: the intermediate shell should ideally form a continuous and natural transition in composition from the core to the outer layer. This helps to achieve minimal lattice mismatch and minimal lattice defects among the core, intermediate shell, and outer shell, thereby achieving the optimal luminescence performance of the core-shell quantum dot material itself. The intermediate shell should generally form a stepped energy level transition from the core to the outer shell. This helps to achieve effective carrier injection and confinement, and reduce lattice interface flicker.
[0145] The optoelectronic devices provided in aspects six through nine of this application may further incorporate optimizations to the hole injection functional layer in the optoelectronic devices of aspects two or three. This may include a first hole injection layer, where the absolute value of the difference between the work function of the first hole injection material and the valence band top energy level of the hole transport material is less than or equal to 0.2 eV. Alternatively, a second hole injection layer may be included, where the difference between the valence band top energy level of the hole transport layer material and the work function of the second hole injection material in the second hole injection layer is less than -0.2 eV. This further improves hole utilization in the device, finely controls the hole injection rate, balances carrier injection within the device, and improves recombination efficiency; simultaneously, it reduces the impact of interface layer charge accumulation on device lifetime.
[0146] The optoelectronic device provided in aspects six to nine of this application may further include an electron transport layer, which comprises at least two stacked sub-electron transport layers; wherein at least one sub-electron transport layer is made of a metal oxometalate transport material. Alternatively, at least one sub-electron transport layer is made of an organic transport material. Alternatively, at least one sub-electron transport layer is made of a metal oxometalate transport material and another sub-electron transport layer is made of an organic transport material.
[0147] Furthermore, as shown in the appendix Figure 10As shown, a tenth aspect of this application provides an optoelectronic device including a quantum dot emitting layer and a hole transport layer. The quantum dot emitting layer contains a core-shell structured quantum dot material, and the outer shell of the quantum dot material is ZnSe. The hole transport material in the hole transport layer has a mobility higher than 1×10⁻⁶. -3 cm 2 / Vs.
[0148] The optoelectronic device provided in aspect ten of this application, due to the relatively shallow valence band energy level (small absolute value of the energy level) and relatively narrow band gap of the ZnSe shell material, has a relatively poor ability to bind excitons in the quantum dot core-shell structure. To ensure good luminescence efficiency of the quantum dot luminescent material itself, a thicker ZnSe shell layer is required, which weakens the rate of hole injection into the luminescent quantum dots through tunneling. The quantum dot layer with a ZnSe shell layer is designed to satisfy the construction of the hole injection barrier between the quantum dot shell layer and the HTL and EML. EML-HTL ≥0.5eV requires the use of HTL materials with high hole mobility, exceeding 1×10⁻⁶. - 3 cm 2 / Vs compensates for the effect of tunneling on hole injection rate, balances the injection efficiency of electrons and holes in the luminescent layer, reduces carrier accumulation, and improves luminescence efficiency.
[0149] In some embodiments, the ZnSe shell thickness in the quantum dot material is 2–5 nm. In this application embodiment, because ZnSe has a relatively narrow band gap and a relatively poor ability to confine excitons in the quantum dot core, a thicker ZnSe shell is required to ensure good luminescence efficiency of the quantum dot core luminescent material itself. The preferred shell thickness is 2.0–5.0 nm. If the shell thickness is too large, the rate at which charge carriers are injected into the luminescent quantum dot through tunneling will decrease; conversely, if the shell thickness is too small, the rate at which charge carriers are injected into the luminescent quantum dot through tunneling will increase. However, when the shell thickness is too small, the shell structure cannot provide sufficient protection and passivation for the core, thus affecting the luminescence performance and stability of the quantum dot material.
[0150] In some embodiments, the emission peak wavelength of the quantum dot material is 510–640 nm. For blue core-shell quantum dots with shorter emission wavelengths and wider core band gaps, even using a thick ZnSe outer shell layer cannot fully guarantee the luminescence efficiency of the quantum dot material itself. Therefore, the preferred quantum dot luminescent material in this application embodiment should be red or green quantum dots with an emission peak wavelength range of 510–640 nm to better ensure the luminescence efficiency of the quantum dots.
[0151] In some embodiments, the valence band top energy level difference between the ZnSe material and the hole transport material is 0.5–1.0 eV. In this embodiment, because the ZnSe outer shell has a relatively thick preferred thickness, the rate at which charge carriers are injected into the luminescent quantum dot via tunneling is weakened. Therefore, the valence band top energy level difference (ΔE) between the corresponding hole transport layer material and the quantum dot outer shell material is relatively large. EML-HTL The value should not be too large; its preferred range should be between 0.5 and 1.0 eV. If ΔE EML-HTL If the size is too large, it will further reduce the efficiency of hole injection into the quantum dot luminescent core, thus affecting the luminescence efficiency of the quantum dot material.
[0152] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is preferably 4.9 eV to 5.4 eV. Within this range, a more suitable hole injection barrier can be constructed with the ZnSe shell material, thereby optimizing the carrier injection and recombination efficiency in the luminescent layer.
[0153] Furthermore, as shown in the appendix Figure 11 As shown, the eleventh aspect of this application provides an optoelectronic device, including a quantum dot emitting layer and a hole transport layer. The quantum dot emitting layer contains a core-shell structured quantum dot material, and the outer shell of the quantum dot material is ZnS. The hole transport material in the hole transport layer has a mobility higher than 1×10⁻⁶. -4 cm 2 / Vs.
[0154] The optoelectronic device provided in the eleventh aspect of this application, when using ZnS as the quantum dot shell material, benefits from the wide band gap of ZnS, which provides strong binding ability for excitons in the quantum dot core-shell structure. A thinner ZnS shell layer is sufficient to maintain the good luminous efficiency of the quantum dot luminescent material itself, thereby increasing the rate at which charge carriers are injected into the luminescent quantum dot via tunneling. The hole mobility of the hole transport material used is greater than or equal to 1 × 10⁻⁶. -4 cm 2 / Vs can simultaneously achieve a hole injection barrier with a valence band top energy level difference greater than or equal to 0.5 eV between the outer shell material and the hole transport material of the quantum dot material. EML-HTL ≥0.5eV, and ensure the efficiency of hole transport and injection into quantum dot materials.
[0155] In some embodiments, the ZnS shell thickness is 0.2–2.0 nm. In this embodiment, because ZnS has a wide band gap and a strong ability to confine excitons in the quantum dot core, a thinner ZnS shell thickness can essentially guarantee the good luminescence efficiency of the quantum dot luminescent material itself; the preferred shell thickness is 0.2–2.0 nm. Simultaneously, the thin ZnS shell can effectively reduce the overall resistance of the device, lower the device driving voltage, and thus improve device performance.
[0156] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is preferably 4.9 eV to 6.0 eV. Within this range, a more suitable hole injection barrier can be constructed with the ZnS shell material, optimizing carrier injection and recombination efficiency in the emitting layer. In some embodiments, the absolute value of the valence band top energy level of the hole transport material is preferably 4.9 eV to 5.5 eV.
[0157] In some embodiments, the valence band top energy level difference between the ZnS material and the hole transport material is 1.0–1.6 eV. In this embodiment, because the ZnS outer shell layer has a relatively thin, preferably thin, carrier injection into the luminescent quantum dot via tunneling is accelerated. Therefore, the valence band top energy level difference (ΔE) between the corresponding hole transport layer material and the quantum dot outer shell material in the quantum dot luminescent layer is significantly increased. EML-HTL The value needs to be appropriately increased to better balance the injection of holes and electrons; its preferred range should be between 1.0 and 1.6 eV. If ΔE EML-HTL If the size is too large, it will further reduce the efficiency of hole injection into the quantum dot luminescent core, thus affecting the luminescence efficiency of the quantum dot material.
[0158] In some embodiments, the emission peak wavelength of the quantum dot material is 400–700 nm. In this application embodiment, because ZnS has a wide band gap and a strong ability to bind excitons in the quantum dot core, it can effectively ensure the luminescence efficiency of the quantum dot material itself. It is applicable to all quantum dot materials in the visible light region with emission peak wavelengths of 400–700 nm, and has a wide range of applications.
[0159] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs.
[0160] Furthermore, as shown in the appendix Figure 12 As shown, the twelfth aspect of this application provides an optoelectronic device, including a quantum dot emitting layer and a hole transport layer. The quantum dot emitting layer contains a core-shell structured quantum dot material, and the outer shell of the quantum dot material is CdZnS. The hole transport material in the hole transport layer has a mobility higher than 1×10⁻⁶. -4 cm 2 / Vs.
[0161] The optoelectronic device provided in the twelfth aspect of this application uses CdZnS as the outer shell layer of the quantum dot. Its band gap width is between that of ZnSe and ZnS, providing a moderate binding ability for excitons in the quantum dot core-shell structure. A relatively moderate CdZnS outer shell layer thickness can essentially guarantee the good luminous efficiency of the quantum dot luminescent material itself; therefore, the outer shell layer thickness has little impact on the tunneling effect of charge carriers. Simultaneously, the valence band energy level of the CdZnS outer shell material is between that of ZnSe and ZnS. To construct the valence band peak energy difference (ΔE... EML-HTL For a hole injection barrier greater than or equal to 0.5 eV, the required valence band top level of the hole transport material is relatively shallow. Therefore, the hole mobility of HTL materials is greater than or equal to 1 × 10⁻⁶. -4 cm 2 When / Vs, the construction of ΔE can be satisfied simultaneously. EML-HTL A hole injection barrier of ≥0.5 eV and ensuring efficient hole transport injection into quantum dot materials.
[0162] In some embodiments, the CdZnS shell thickness is 0.5–3.0 nm. Since the band gap of CdZnS is between that of ZnSe and ZnS, a preferred shell thickness of 0.5–3.0 nm can simultaneously ensure the binding ability of excitons in the quantum dot core and the good luminescence efficiency of the quantum dot luminescent material itself.
[0163] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.9 eV. Within this range, a more suitable hole injection barrier can be constructed with the CdZnS shell material, optimizing carrier injection and recombination efficiency in the luminescent layer. In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.5 eV.
[0164] In some embodiments, the valence band top energy level difference between the CdZnS material and the hole transport material is 0.8–1.4 eV. The valence band top energy level difference (ΔE) between the hole transport layer material and the quantum dot outer shell material in the quantum dot emitting layer in this application embodiment is shown in the figure. EML-HTL The preferred range is 0.8–1.4 eV, which ensures both the efficiency of carrier injection into the luminescent quantum dot via tunneling and a good balance between the injection efficiency of holes and electrons. If ΔE EML-HTL If ΔE is too large, the efficiency of carriers being injected into the luminescent quantum dot core through tunneling will decrease; if ΔE EML-HTL If the value is too small, the injection rate of holes will not be well regulated.
[0165] In some embodiments, the emission peak wavelength of the quantum dot material is 400–700 nm. In this application, because CdZnS has a relatively strong binding ability to excitons in the quantum dot core, it can effectively ensure the luminescence efficiency of the quantum dot material itself. This makes it applicable to all quantum dot materials in the visible light region with emission peak wavelengths of 400–700 nm, thus having a wide range of applications.
[0166] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs.
[0167] Furthermore, as shown in the appendix Figure 13 As shown, the thirteenth aspect of this application provides an optoelectronic device, including a quantum dot emitting layer and a hole transport layer. The quantum dot emitting layer contains a core-shell structured quantum dot material, and the outer shell of the quantum dot material is ZnSeS. The hole transport material in the hole transport layer has a mobility higher than 1×10⁻⁶. -4 cm 2 / Vs.
[0168] The optoelectronic device provided in aspect thirteen of this application uses ZnSeS as the outer shell layer of the quantum dot. Its band gap width is between that of ZnSe and ZnS, providing moderate exciton binding ability in the quantum dot core-shell structure, while having minimal impact on carrier tunneling. Simultaneously, the valence band energy level of the ZnSeS outer shell material is between that of ZnSe and ZnS, requiring the construction of a valence band top energy level difference (ΔE). EML-HTL For a hole injection barrier greater than or equal to 0.5 eV, the required valence band top level of the hole transport material is relatively shallow. Therefore, the hole mobility of HTL materials is greater than or equal to 1 × 10⁻⁶. -4 cm 2 When the value is / Vs, it is possible to simultaneously satisfy the requirements of constructing a hole injection barrier and ensuring the efficiency of hole transport injection into the quantum dot material.
[0169] In some embodiments, the ZnSeS shell thickness is 1.0 to 4.0 nm. Since the easily oxidized Se in the ZnSeS shell is closer to the quantum dot surface, the ZnSeS shell needs to be thicker to ensure sufficient protection and passivation for the core. Therefore, the preferred ZnSeS shell thickness is 1.0 to 4.0 nm.
[0170] In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.7 eV. Within this range, a more suitable hole injection barrier can be constructed with the ZnSeS shell material, optimizing carrier injection and recombination efficiency in the luminescent layer. In some embodiments, the absolute value of the valence band top energy level of the hole transport material is 4.9–5.4 eV.
[0171] In some embodiments, the valence band top energy level difference between the ZnSeS material and the hole transport material is 0.9–1.4 eV. The valence band top energy level difference (ΔE) between the hole transport layer material and the quantum dot outer shell material in the quantum dot emitting layer of this application embodiment is shown in the figure. EML-HTL When the preferred voltage range is 0.9–1.4 eV, it can ensure the efficiency of carrier injection into the luminescent quantum dot through tunneling, while also achieving a good balance between the injection efficiency of holes and electrons. If ΔE EML-HTL If ΔE is too large, the efficiency of carriers being injected into the luminescent quantum dot core through tunneling will decrease; if ΔE EML-HTL If the value is too small, the injection rate of holes will not be well regulated.
[0172] In some embodiments, the emission peak wavelength of the quantum dot material is 400–700 nm. In this application, because ZnSeS has a relatively strong binding ability to excitons in the quantum dot core, it can effectively ensure the luminescence efficiency of the quantum dot material itself. This makes it suitable for all quantum dot materials in the visible light region with emission peak wavelengths of 400–700 nm, thus having a wide range of applications.
[0173] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs.
[0174] In the optoelectronic devices provided in aspects 10 to 13 of this application, the hole transport material is selected from at least one of: polymers containing aniline groups, copolymers containing fluorene groups and aniline groups. In practical applications, a hole transport material with a suitable mobility can be selected according to specific application requirements.
[0175] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 Polymers containing aniline groups in / Vs include: poly-TPD, TFB, P9, P11, and P13.
[0176] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -3 cm 2 / Vs copolymers containing fluorene and aniline groups include: TFB and P13.
[0177] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -4 cm 2 Polymers containing aniline groups in / Vs include: poly-TPD, TFB, P9, P11, P13, and P15.
[0178] In some embodiments, the mobility of the hole transport material is greater than 1×10⁻⁶. -4 cm 2The copolymers containing fluorene and aniline groups of / Vs include: TFB, P13, and P15.
[0179] In the optoelectronic devices provided in aspects 10 to 13 of this application, the core-shell structured quantum dot material further includes a core and an intermediate shell layer located between the core and the outer shell layer; wherein, the valence band top energy level of the core material is shallower than the valence band top energy level of the outer shell layer material; and the valence band top energy level of the intermediate shell layer material is between the valence band top energy level of the core material and the valence band top energy level of the outer shell layer material.
[0180] In some embodiments, the core material is selected from at least one of the following semiconductor compounds: Groups II-IV, II-VI, II-V, III-V, III-VI, IV-VI, I-III-VI, II-IV-VI, and II-IV-V of the periodic table. In some specific embodiments, the core material is selected from at least one of the following: CdSe, CdZnSe, CdSeS, CdZnSeS, InP, InGaP, GaP, ZnTe, and ZnTeSe. These core materials have good luminescent properties and exhibit good compatibility with the outer shell layer ZnSe, ZnS, CdZnS, or ZnSeS.
[0181] In some specific embodiments, the intermediate shell material is selected from at least one of CdZnSe, ZnSe, CdZnS, CdZnSeS, CdS, and CdSeS. The principle for matching the intermediate shells in this application is as follows: the intermediate shell should ideally form a continuous and natural transition in composition from the core to the outer layer. This helps to achieve minimal lattice mismatch and minimal lattice defects among the core, intermediate shell, and outer shell, thereby achieving the optimal luminescence performance of the core-shell quantum dot material itself. The intermediate shell should generally form a stepped energy level transition from the core to the outer shell. This helps to achieve effective carrier injection and confinement, and reduce lattice interface flicker.
[0182] The optoelectronic devices provided in aspects 10 to 13 of this application may further incorporate optimizations to the hole injection functional layer in the optoelectronic devices of aspects 2 or 3 above. This optimization may include a first hole injection layer, where the absolute value of the difference between the work function of the first hole injection material and the valence band top energy level of the hole transport material is less than or equal to 0.2 eV. Alternatively, it may include a second hole injection layer, where the difference between the valence band top energy level of the hole transport layer material and the work function of the second hole injection material in the second hole injection layer is less than -0.2 eV. This further improves hole utilization in the device, finely controls the hole injection rate, balances carrier injection within the device, and improves recombination efficiency; simultaneously, it reduces the impact of interface layer charge accumulation on device lifetime.
[0183] The optoelectronic device provided in aspects 10 to 13 of this application may further include an electron transport layer, which comprises at least two stacked sub-electron transport layers; wherein the material of at least one sub-electron transport layer is a metal oxometalate transport material. Alternatively, the material of at least one sub-electron transport layer is an organic transport material. Alternatively, it may simultaneously include a metal oxometalate transport material for one sub-electron transport layer and an organic transport material for one sub-electron transport layer.
[0184] In the above embodiments of this application, the device is not limited by the device structure and can be a positive structure device or a negative structure device.
[0185] In one embodiment, the positive structure optoelectronic device includes a stacked structure of an anode and a cathode disposed opposite each other, a light-emitting layer disposed between the anode and the cathode, and the anode being disposed on a substrate. Further, a hole functional layer such as a hole injection layer and a hole transport layer may be disposed between the anode and the light-emitting layer; and an electron functional layer such as an electron transport layer and an electron injection layer may be disposed between the cathode and the light-emitting layer, as shown in the attached figure. Figure 14 As shown. In some specific positive structure device embodiments, the optoelectronic device includes a substrate, an anode disposed on the surface of the substrate, a hole transport layer disposed on the surface of the anode, a light-emitting layer disposed on the surface of the hole transport layer, an electron transport layer disposed on the surface of the light-emitting layer, and a cathode disposed on the surface of the electron transport layer.
[0186] In one embodiment, the inverted optoelectronic device includes a stacked structure of an anode and a cathode disposed opposite each other, a light-emitting layer disposed between the anode and the cathode, and the cathode being disposed on a substrate. Further, a hole functional layer such as a hole injection layer and a hole transport layer may be disposed between the anode and the light-emitting layer; and an electron functional layer such as an electron transport layer and an electron injection layer may be disposed between the cathode and the light-emitting layer, as shown in the attached figure. Figure 15 As shown. In some embodiments of inverted structure devices, the optoelectronic device includes a substrate, a cathode disposed on the surface of the substrate, an electron transport layer disposed on the surface of the cathode, a light-emitting layer disposed on the surface of the electron transport layer, a hole transport layer disposed on the surface of the light-emitting layer, and an anode disposed on the surface of the hole transport layer.
[0187] In some embodiments, the choice of substrate is not limited; a rigid substrate or a flexible substrate can be used. In some specific embodiments, the rigid substrate includes, but is not limited to, one or more of glass and metal foil. In some specific embodiments, the flexible substrate includes, but is not limited to, one or more of polyethylene terephthalate (PET), polyethylene terephthalate (PEN), polyetheretherketone (PEEK), polystyrene (PS), polyethersulfone (PES), polycarbonate (PC), polyarylate (PAT), polyarylate (PAR), polyimide (PI), polyvinyl chloride (PV), polyethylene (PE), polyvinylpyrrolidone (PVP), and textile fibers.
[0188] In some embodiments, the selection of the anode material is not limited and can be selected from doped metal oxides, including but not limited to one or more of indium-doped tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), magnesium-doped zinc oxide (MZO), and aluminum-doped magnesium oxide (AMO). It can also be selected from composite electrodes consisting of doped or undoped transparent metal oxides sandwiching a metal, including but not limited to one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2.
[0189] In some embodiments, the cathode material can be one or more of various conductive carbon materials, conductive metal oxide materials, and metallic materials. In some specific embodiments, the conductive carbon material includes, but is not limited to, doped or undoped carbon nanotubes, doped or undoped graphene, doped or undoped graphene oxide, C60, graphite, carbon fibers, porous carbon, or mixtures thereof. In some specific embodiments, the conductive metal oxide material includes, but is not limited to, ITO, FTO, ATO, AZO, or mixtures thereof. In some specific embodiments, the metallic material includes, but is not limited to, Al, Ag, Cu, Mo, Au, or alloys thereof; wherein the metallic material has a morphology including, but is not limited to, dense thin films, nanowires, nanospheres, nanorods, nanocones, hollow nanospheres, or mixtures thereof; preferably, the cathode is Ag or Al.
[0190] In some embodiments, the thickness of the quantum dot emitting layer is 8–100 nm. In some embodiments, the thickness of the hole transport layer is 10–150 nm. In some embodiments, the thickness of the electron transport layer is 10–200 nm. In practical applications, the electron functional layer, emitting layer, and hole functional layer in the device can be designed with appropriate thicknesses according to the characteristics of the device in the above embodiments.
[0191] The fabrication of the optoelectronic device in this application includes the following steps:
[0192] S10. Obtain a substrate with an anode deposited on it;
[0193] S20. A hole injection layer is grown on the anode surface;
[0194] S30. A hole transport layer is grown on the surface of the hole injection layer;
[0195] S40. Next, a quantum dot luminescent layer is deposited on the hole transport layer;
[0196] S50. Finally, an electron transport layer is deposited on the quantum dot light-emitting layer, and a cathode is deposited on the electron transport layer to obtain an optoelectronic device.
[0197] Specifically, in step S10, the ITO substrate needs to undergo a pretreatment process, which includes: cleaning the ITO conductive glass with a cleaning agent to initially remove the stains on the surface, then ultrasonically cleaning it for 20 minutes in deionized water, acetone, anhydrous ethanol, and deionized water respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen to obtain the ITO positive electrode.
[0198] Specifically, in step S20, the step of growing the hole injection layer includes: preparing a thin film in the QLED device by means of a solution method, a vacuum sputtering method, or a vacuum evaporation method; wherein, the solution method includes inkjet printing, spin coating, spray printing, slot-die printing, or screen printing, etc.
[0199] Specifically, in step S30, the step of growing the hole transport layer includes: placing the ITO substrate on a spin coater and spin-coating a film with a prepared solution of hole transport material; controlling the film thickness by adjusting the concentration of the solution, the spin coating speed and the spin coating time, and then performing thermal annealing at an appropriate temperature.
[0200] Specifically, in step S40, the step of depositing the quantum dot luminescent layer on the hole transport layer includes: placing the substrate with the hole transport layer already spin-coated on a spin coater, spin-coating a luminescent material solution of a certain concentration into a film, controlling the thickness of the luminescent layer (approximately 20–60 nm) by adjusting the concentration of the solution, the spin-coating speed, and the spin-coating time, and drying at an appropriate temperature.
[0201] Specifically, in step S50, the step of depositing the electron transport layer on the quantum dot light-emitting layer includes: placing the substrate with the quantum dot light-emitting layer already spin-coated on a spin coater; spin-coating a prepared electron transport composite material solution of a certain concentration into a film through processes such as drop coating, spin coating, immersion, coating, printing, and vapor deposition; controlling the thickness of the electron transport layer, approximately 20-60 nm, by adjusting the concentration of the solution, the spin coating speed (preferably, the rotation speed is between 3000 and 5000 rpm), and the spin coating time; and then annealing the film at 150°C to 200°C to fully remove the solvent.
[0202] Specifically, in step S60, the cathode preparation step includes: placing the substrate after the deposition of each functional layer in a vapor deposition chamber and thermally vapor-depositing a 60-100nm layer of metallic silver or aluminum as the cathode using a mask.
[0203] In some embodiments, the method for fabricating the optoelectronic device further includes encapsulating the stacked optoelectronic device; the curing resin used for encapsulation is an acrylic resin, an acrylate resin, or an epoxy resin; the resin curing is performed by UV irradiation, heating, or a combination of both. Encapsulation can be performed using common machine encapsulation or manually. Preferably, the oxygen and water content in the encapsulation environment is both below 0.1 ppm to ensure device stability.
[0204] In some embodiments, the method for fabricating an optoelectronic device further includes, after encapsulating the optoelectronic device, introducing one or more processes including ultraviolet irradiation, heating, positive and negative pressure, external electric field, and external magnetic field; the atmosphere at which the process is applied can be air or an inert atmosphere.
[0205] To enable those skilled in the art to clearly understand the above-described implementation details and operations, and to demonstrate the significant advancements in the performance of the optoelectronic devices in the embodiments of this application, the following examples illustrate the above technical solutions.
[0206] The devices in this application adopt an ITO / HIL / HTL / QD / ETL / AL structure. After packaging, they undergo a certain heat treatment. The advantages of the technical solution in this application are explained in detail by comparing the combination of different functional layers in the device. In the following embodiments, the lifetime test uses the constant current method, at a constant 50mA / cm². 2Driven by current, a silicon photonics system is used to test the brightness change of the device. The time (LT95) during which the device brightness decays from its highest point to 95% of its maximum brightness is recorded. Then, the device's lifetime of 1000 nits (LT95S) is extrapolated using an empirical formula. This method facilitates the comparison of lifetimes of devices with different brightness levels and has wide applications in practical optoelectronic devices.
[0207] 1000nit LT95=(L Max / 1000) 1.7 ×LT95
[0208] The energy level testing method for each material in this application embodiment is as follows: after spin-coating each functional layer material into a film, the energy level is tested using the UPS (ultraviolet photoelectron spectroscopy) method.
[0209] Work function Φ=hν-E cutoff Where hv is the energy of the incident excited photon, E cutoff The cutoff position for the excited secondary electrons;
[0210] Price band top VB (HOMO): E HOMO =E F-HOMO +Φ, where E F-HOMO The difference between the HOMO (VB) and Fermi level of the material corresponds to the starting edge of the first peak appearing at the low binding energy end in the binding energy spectrum;
[0211] LOMO (Local Module Outer Motion): E LOMO =E HOMO -E HOMO-LOMO , of which E HOMO-LOMO The band gap of the material is obtained from UV-Vis (ultraviolet absorption spectroscopy).
[0212] Examples 1-7
[0213] To verify the impact of the hole injection barrier between the outer shell material and the hole transport material of quantum dot materials on device performance, this application sets up Examples 1 to 7, which illustrate the impact of the hole injection barrier on device lifetime and other performance characteristics by comparing different combinations of HTL and QD.
[0214] The two types of quantum dots used in Examples 1-7 of this application are: blue QD1 with a CdZnS shell (core CdZnSe, middle shell ZnSe, shell thickness 1.5 nm, valence band top energy level -6.2 eV) and blue QD2 with a ZnS shell (core CdZnSe, middle shell ZnSe, ZnS shell thickness 0.3 nm, valence band top energy level 6.5 eV). The hole transport material for blue QD3 with a ZnSeS shell (core CdZnSe, middle shell ZnSe) is P9(E... HOMO:5.1eV), P15(E HOMO :5.8eV), the hole injection layer uses PEDOT:PSS(E HOMO (5.1 eV), the electron transport layer is made of ZnO, as shown in Table 1 below:
[0215] Table 1
[0216]
[0217] From Table 1 above and appendix Figure 16 The test results (horizontal axis represents time, vertical axis represents brightness) show that for the same CdZnS (6.2eV) shell quantum dot, changing the HTL from P15 (5.8eV) to P9 (5.1eV) results in a decrease in ΔE. EML-HTL Increasing the potential barrier difference from 0.4 eV to 1.1 eV improved device lifetime; the lifetime of the 1000 nit LT95S increased from 0.72 to 1.26. Furthermore, for the same P15 (5.8 eV) material, changing the quantum dot shell from CdZnS (6.2 eV) to ZnS (6.5 eV) improved ΔE. EML-HTL The barrier difference increased from 0.4 eV to 0.7 eV, resulting in a significant improvement in device lifetime. The lifetime of the 1000 nit LT95S increased from 0.72 to 6.29.
[0218] Therefore, it can be seen that whether adjusting the HTL or EML materials, the difference ΔE at the top of the valence band is... EML-HTL Increasing the voltage to above 0.5 eV optimizes the device injection balance and enhances device lifetime. This indicates that by raising the hole injection barrier to reduce hole injection efficiency, a better balance between hole and electron injection in the emissive layer can be achieved, thereby improving device luminous efficiency and lifetime.
[0219] Examples 8-11
[0220] Furthermore, to verify the impact of the HIL-HTL interface energy level barrier on device performance, this application provides Examples 8-11, which illustrate the effect of ΔE by comparing different HTL and HTL pairings. HTL-HIL The impact of hole injection barrier on device lifetime and other performance characteristics.
[0221] In Examples 8-9 of this application, blue quantum dots with a ZnS outer shell (core of CdZnSe, middle shell of ZnSe, shell thickness of 0.3 nm, valence band top energy level of 6.5 eV) are used. In Examples 10-11, red quantum dots with a ZnS outer shell (core of CdZnSe, middle shell of ZnSe, shell thickness of 0.3 nm, valence band top energy level of 6.5 eV) are used. The hole transport materials are P9(E) and ... HOMO :5.5eV), P11(EHOMO 5.5eV), P13(E HOMO :4.9eV), the hole injection layer uses PEDOT:PSS(E HOMO HIL2 (power function: 5.1 eV) and HIL3 (power function: 5.6 eV), with ZnO used for the electron transport layer, as shown in Table 2 below:
[0222] Table 2
[0223]
[0224] Note: When ΔE HTL-HIL When <0.2 eV, under the existing HIL materials and experimental data, ΔE EML-HTL It must be greater than 0.5 eV.
[0225] From Table 2 and Appendix Figure 17 and 18 (The horizontal axis represents time, and the vertical axis represents brightness.) The test results show that, compared to the blue quantum dot devices in Examples 8 and 9, and the red quantum dot devices in Examples 10 and 11, the hole injection energy level barrier ΔE between HTL and HIL is relatively smaller. HTL-HIL When <-0.2eV, relative to ΔE HTL-HIL In embodiments with a voltage greater than or equal to -0.2 eV, the device lifetime of 1000 nits for the LT95S is further improved. This indicates that increasing the hole injection barrier from the anode to the HIL reduces the overall hole injection rate within the QLED device, effectively controlling the number of holes entering the QLED device. This not only improves carrier recombination efficiency but also reduces excessive hole injection leading to charge accumulation at the HTL and HIL interface, thereby improving the device's luminescence lifetime.
[0226] Examples 12-19
[0227] Furthermore, to verify the impact of the HIL-HTL interface energy level barrier on device performance, this application provides Examples 12-19, which illustrate the effect of |ΔE| on device performance through comparisons of different HTL pairings. HTL-HIL The impact of hole injection barrier on device performance such as drive voltage.
[0228] In Examples 12-14 of this application, blue quantum dots with a ZnS shell (core of CdZnSe, middle shell of ZnSe, shell thickness of 0.3 nm, valence band top energy level of 6.5 eV) are used. In Examples 15-19, red quantum dots with a ZnS shell (core of CdZnSe, middle shell of ZnSe, shell thickness of 0.3 nm, valence band top energy level of 6.5 eV) are used. The hole transport material is P9(E) HOMO 5.5eV), P13(E HOMO:4.9eV), TFB(E HOMO :5.4eV), the hole injection layer uses PEDOT:PSS(E HOMO HIL1-1 (power function: 5.1 eV) and HIL1-2 (power function: 5.3 eV), with ZnO used for the electron transport layer, as shown in Table 3 below:
[0229] Table 3
[0230]
[0231]
[0232] From Table 3 and Appendix Figure 19 and 20 (The horizontal axis represents time, and the vertical axis represents voltage.) The test results show that when the hole injection energy level barrier |ΔE between HTL and HIL is reached... HTL-HIL When | less than or equal to 0.2 eV, relative to |ΔE HTL-HIL In embodiments with a potential barrier greater than 0.2, charge accumulation on the hole transport side of the device is minimal. Under prolonged constant current operation, the increase in the device's driving voltage is significantly reduced, resulting in a device lifetime of 1000 nits (LT95S). Simultaneously, when the barrier difference between HIL and HTL is small, there is almost no charge accumulation at the interface, no aging on the opposite side, stable hole injection capability, and further improved device lifetime. This demonstrates that lowering the hole injection level barrier facilitates effective hole injection from HIL to HTL, eliminates the barrier and interface charge, reduces the overall device resistance, and thus improves device lifetime.
[0233] Examples 20-25
[0234] Furthermore, to verify the impact of hole transport layer materials on device performance, this application provides Examples 20-25, which compare different combinations of HTL materials to illustrate the impact of HTL materials on the construction of hole injection barriers, optimization of carrier recombination efficiency, and device lifetime and other performance aspects.
[0235] In embodiments 20-25 of this application, blue quantum dots with a ZnS outer shell (core of CdZnSe, middle shell of ZnSe, shell thickness of 0.3 nm, valence band top energy level of 6.5 eV) are used, and the hole transport material is P12(E HOMO 5.8eV), P13(E HOMO :4.9eV), TFB(E HOMO :5.4eV), the hole injection layer uses PEDOT:PSS(E HOMO (5.1 eV), as shown in Table 4 below:
[0236] Table 4
[0237]
[0238]
[0239] From Table 4 and Appendix Figure 21 (The horizontal axis represents time, and the vertical axis represents brightness.) Test results show that materials with different energy levels can be mixed in the hole transport layer to flexibly control ΔE. EML-HTL Injecting a potential barrier to construct ΔE EML-HTL A potential barrier of ≥0.5 eV is used to reduce the hole injection rate within the QLED device, thereby controlling carrier injection and recombination efficiency. Simultaneously, it reduces the irreversible damage to device lifetime performance caused by charge accumulation at the HIL and HTL interface. Furthermore, test results show that devices with hybrid hole transport layers have better luminous lifetime. Deep-level HTLs can reduce brightness variations during lifetime testing caused by exciton transfer between HTL and QD, thus shortening the rise time. Therefore, by mixing shallow and deep levels, device lifetime can be guaranteed while reducing the brightness rise time, allowing the device to quickly reach a stable state, which is beneficial for subsequent testing and applications. (See attached diagram.) Figure 21 Comparing Examples 22, 24, and 25, it can be seen that from Examples 22 to 24 to 25, the proportion of deep-level material doping increases, and the lifetimes are all between 60 and 80 hours with little difference. The brightness rise times in the tests are approximately 7 hours, 5 hours, and 4 hours, respectively. Compared with Example 21, Examples 22, 24, or 25 have a higher proportion of deep-level material, a greater range of control over the mobility of hole transport material, and are more likely to produce quantum dot devices with longer lifetimes.
[0240] Examples 26-28
[0241] Furthermore, in Examples 26-28, when the outer shell of the blue quantum dot material is ZnS (with a core of CdZnSe, an intermediate shell of ZnSe, and a shell thickness of 0.2-2.0 nm), in order to construct a suitable ΔE EML-HTL Energy level barrier: The absolute value of the valence band top energy level of the hole transport material must be less than or equal to 6.0 eV, as shown in Table 5, Examples 26-28 below (the hole injection layer uses PEDOT:PSS(E HOMO (5.1 eV), the electron transport layer is made of ZnO:
[0242] Table 5
[0243]
[0244] From Table 5 and Appendix Figure 22(The horizontal axis represents time, and the vertical axis represents brightness.) Test results show that when the outer shell of the quantum dot emitting layer is ZnS and the thickness of the outer shell is 0.2–2.0 nm, the preferred hole transport layer material and the valence band top energy level difference (ΔE) between the outer shell material and the quantum dot emitting layer material in the quantum dot emitting layer are... EML-HTL The range is 1.0 to 1.6 eV, at which point the device has a better luminescence lifetime.
[0245] Examples 29-31
[0246] Furthermore, in Examples 29-31, when the outer shell of the blue quantum dot material is ZnSe (the core is CdZnSe, the middle shell is ZnSe, and the outer shell thickness is 2-5 nm), in order to construct a suitable ΔE EML-HTL Energy level barrier: The absolute value of the valence band top energy level of the hole transport material must be less than or equal to 5.4 eV, as shown in Table 6, Examples 29-31 below (the hole injection layer uses PEDOT:PSS(E HOMO (5.1 eV), the electron transport layer is made of ZnO:
[0247] Table 6
[0248]
[0249] From Table 6 and Appendix Figure 23 (The horizontal axis represents time, and the vertical axis represents brightness.) Test results show that when the outer shell of the quantum dot emitting layer is ZnS and the thickness of the outer shell is 2–5 nanometers, the preferred hole transport layer material and the valence band top energy level difference (ΔE) between the outer shell material and the quantum dot emitting layer material are... EML-HTL The range is 0.5–1.0 eV, at which point the device has a better luminescence lifetime.
[0250] Examples 32-35
[0251] Furthermore, in Examples 32-35, when the outer shell of the blue quantum dot material is CdZnS (with a CdZnSe core, a ZnSe middle shell, and an outer shell thickness of 0.5-3.0 nm), in order to construct a suitable ΔE EML-HTL Energy level barrier: The absolute value of the valence band top energy level of the hole transport material must be less than or equal to 5.9 eV, as shown in Table 7, Examples 32-35 below (the hole injection layer uses PEDOT:PSS(E HOMO (5.1 eV), the electron transport layer is made of ZnO:
[0252] Table 7
[0253]
[0254] From Table 7 and Appendix Figure 24(The horizontal axis represents time, and the vertical axis represents brightness.) Test results show that when the outer shell of the quantum dot emitting layer is CdZnS and the thickness of the outer shell is 0.5-3.0 nanometers, the preferred hole transport layer material and the valence band top energy level difference (ΔE) between the outer shell material and the quantum dot emitting layer material are optimal. EML-HTL The range is 0.8-1.4 eV, at which point the device has a better luminescence lifetime.
[0255] Examples 36-38
[0256] Furthermore, in Examples 36-38, when the outer shell of the blue quantum dot material is ZnSeS (the core is CdZnSe, the middle shell is ZnSe, and the outer shell thickness is 1.0-4.0 nm), in order to construct a suitable ΔE EML-HTL Energy level barrier: The absolute value of the valence band top energy level of the hole transport material must be less than or equal to 5.7 eV, as shown in Table 8, Examples 36-38 below (the hole injection layer uses PEDOT:PSS(E HOMO (5.1 eV), the electron transport layer is made of ZnO:
[0257] Table 8
[0258]
[0259] From Table 8 and Appendix Figure 24 (The horizontal axis represents time, and the vertical axis represents brightness.) Test results show that when the outer shell of the quantum dot emitting layer is CdZnS and the thickness of the outer shell is 0.5-3.0 nanometers, the preferred hole transport layer material and the valence band top energy level difference (ΔE) between the outer shell material and the quantum dot emitting layer material are optimal. EML-HTL The range is 0.9-1.4 eV, at which point the device has a better luminescence lifetime.
[0260] Examples 39-43
[0261] Furthermore, to verify the impact of the hole injection layer on device performance, this application provides the following embodiments. In embodiments 39-41, red quantum dots with a ZnS outer shell (a CdZnSe core, a ZnSe middle shell, and a valence band top energy level of 6.5 eV) are used. In embodiments 42-43, red quantum dots with a ZnS outer shell (a CdZnSe core, a ZnSe middle shell, and a valence band top energy level of 6.5 eV) are used, and the electron transport layer is ZnO. As shown in Table 9:
[0262] Table 9
[0263]
[0264] From Table 9 and Appendix Figure 26 and 28(The horizontal axis represents time, and the vertical axis represents voltage), and attached... Figure 27 and 29 (The horizontal axis represents time, and the vertical axis represents brightness.) Test results show that after removing the HIL layer, the charge accumulation between the hole injection layer and the hole transport layer, as well as the effects of acidic PEDOT on the device, disappear. Under long-term constant current operation, the device's driving voltage remains almost unchanged; in fact, it even shows a downward trend because the charge fills the defects within the device. Using P11 material with higher mobility to fabricate a HIL-free device, the driving voltage decreases more significantly under long-term constant current operation, indicating that the preferred HTL mobility is higher than 1x10⁻⁶. -3 cm 2 / Vs can achieve better suppression of device voltage rise.
[0265] Furthermore, when inorganic metal oxide MoO3 is used instead of organic PEDOT:PSS as the hole injection layer material, the voltage rise of the device during operation is significantly reduced compared to devices with organic hole injection layer materials because the destruction of MoO3 hole injection material is effectively suppressed. At the same time, the measured lifetime of the device is also effectively improved.
[0266] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. An optoelectronic device, characterized in that, include: The device comprises an anode, a hole transport layer on the anode, a quantum dot luminescent layer on the hole transport layer, and a cathode on the quantum dot luminescent layer. The quantum dot luminescent layer contains a core-shell quantum dot material, and the outer shell of the quantum dot material is ZnSeS material. The energy difference between the valence band top of the ZnSeS material and the hole transport material in the hole transport layer is 1.0 eV to 1.4 eV, which is used to increase the hole injection barrier to reduce the hole injection efficiency. The absolute value of the valence band top of the hole transport material in the hole transport layer is less than or equal to 5.7 eV. The thickness of the ZnSeS shell in the quantum dot material is 1.0 to 4.0 nm.
2. The optoelectronic device as described in claim 1, characterized in that, The emission peak wavelength of the quantum dot material is 400~700 nm.
3. The optoelectronic device as described in claim 2, characterized in that, The absolute value of the valence band top energy level of the hole transport material is 4.9~5.7 eV.
4. The optoelectronic device as described in claim 3, characterized in that, The core-shell structured quantum dot material further includes a core and an intermediate shell layer located between the core and the outer shell layer; wherein, The valence band top energy level of the core material is shallower than that of the outer shell material; The valence band top level of the intermediate shell material lies between the valence band top level of the core material and the valence band top level of the outer shell material.
5. The optoelectronic device as described in claim 4, characterized in that, The core material is selected from at least one of the following: semiconductor compounds from Groups II-IV, II-VI, II-V, III-V, III-VI, IV-VI, I-III-VI, II-IV-VI, and II-IV-V of the periodic table; And / or, the core material is selected from at least one of: CdSe, CdZnSe, CdSeS, CdZnSeS, InP, InGaP, GaP, ZnTe, and ZnTeSe; And / or, the intermediate shell material is selected from at least one of: CdZnSe, ZnSe, CdZnS, CdZnSeS, CdS, and CdSeS.
6. The optoelectronic device as described in any one of claims 1, 3 to 5, characterized in that, And / or, the hole transport material is selected from at least one of: polymers containing aniline groups, copolymers containing fluorene groups and aniline groups.
7. The optoelectronic device as described in claim 6, characterized in that, The aniline-containing polymer includes at least one of P9 and P13; And / or, the copolymer containing fluorene groups and aniline groups includes: P13; And / or, the absolute value of the valence band top energy level of the hole transport material is 4.9~5.4 eV.
8. The optoelectronic device as described in claim 7, characterized in that, The optoelectronic device further includes a first hole injection layer, wherein the absolute value of the difference between the work function of the first hole injection material and the valence band top energy level of the hole transport material is less than or equal to 0.2 eV. Alternatively, the optoelectronic device may further include a second hole injection layer, wherein the difference between the valence band top energy level of the hole transport material and the work function of the second hole injection material in the second hole injection layer is less than -0.2 eV.
9. The optoelectronic device as described in claim 8, characterized in that, The optoelectronic device further includes an electron transport layer, which comprises at least two stacked sub-electron transport layers. Wherein, at least one sub-electron transport layer is made of a metal oxometalate transport material; and / or, at least one sub-electron transport layer is made of an organic transport material.
Citation Information
Patent Citations
Quantum dot electroluminescent device and display
CN108963087A
Quantum dot device and electronic device
CN110246973A
Quantum dot device and electronic device
CN111435710A
